A reinforced glass ceramic with high strength and its application
By introducing (Zn, Mg)Al2O4 and tetragonal ZrO2 crystal phases into glass ceramics, the depth and deep stress of their compression stress layer are improved, and the problem of existing glass products are easily broken when falling is solved, achieving high mechanical strength and excellent resistance. Reinforced glass ceramics with drop performance.
Patent Information
- Application Number
- CN202311800642.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-12-25
AI Technical Summary
Existing glass products are prone to break when falling, mainly due to insufficient depth of the compressive stress layer and small deep stress, they cannot effectively offset the energy during falling.
Developed a reinforced glass ceramic that contains the main crystal phase (Zn, Mg) Al2O4 crystal phase and the secondary crystal phase tetragonal ZrO2 crystal phase, with ultra-high compression stress layer depth and large deep stress, through specific crystal phase structure and Stress structures work together to improve the mechanical strength and fall impact resistance of glass ceramics.
The high mechanical strength and excellent anti-fall impact performance of reinforced glass ceramics are achieved, and can maintain integrity at a higher drop height while maintaining high light transmittance.
Smart Images

Figure CN117776534B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass ceramics, and in particular to a reinforced glass ceramic with high strength and application thereof. Background Art
[0002] The most common situation of electronic equipment protective glass breaking is falling and breaking. Analyzing the falling process, it is roughly due to the collision of the glass surface with a sharp object (such as fine sand, cement, pebbles) with a hardness equal to or greater than that of the glass surface, resulting in local damage, forming a hemispherical crack extension source at the damage point, and the collision energy is partially attenuated. The remaining energy further expands. When the compressive stress level on the glass surface is not enough to offset the remaining energy, the crack extension will pass through the glass surface area. When the longitudinal crack passes through the depth of the compressive stress layer to the tensile stress layer (or also called, tensile stress layer) area, the crack will quickly expand in the tensile stress area, so that the crack penetrates the entire glass, thus causing the glass to break or fracture.
[0003] It can be seen that the depth of the compressive stress layer and the deep stress of glass products are closely related to their anti-drop damage performance. When the depth of the compressive stress layer is constant, the greater the deep stress, the more residual energy of the drop collision can be offset by the surface compressive stress level. When the surface compressive stress level is not enough to offset the residual energy of the drop collision, the deeper the depth of the compressive stress layer of the glass, the more conducive it is to offset the energy that drives the crack extension.
[0004] Therefore, in order to further improve the drop impact resistance of glass ceramics, it is necessary to develop a reinforced glass ceramic with large deep stress and ultra-high compressive stress layer depth and high mechanical strength, especially a high-strength transparent reinforced glass ceramic with excellent light transmittance or transmittance. Summary of the invention
[0005] The purpose of the present application is to provide a high-strength reinforced glass-ceramic and its application, wherein the reinforced glass-ceramic has a large deep stress and an ultra-high compressive stress layer depth, forming a specific stress structure, thereby giving the reinforced glass-ceramic excellent drop impact resistance.
[0006] The technical solutions provided by this application are as follows:
[0007] In a first aspect, a strengthened glass ceramic is provided, wherein the strengthened glass ceramic comprises a main crystalline phase (Zn, Mg)Al 2 O 4 Crystalline phase and minor crystal phase tetragonal ZrO 2Crystalline phase; the reinforced glass ceramic comprises a compressive stress layer region extending from the surface of the reinforced glass ceramic to the compression depth, and has a tensile stress layer region inside; the compressive stress layer depth DOL_0 of the reinforced glass ceramic is ≥ 0.21t, preferably, 0.21t≤DOL_0≤0.25t, t is the thickness of the reinforced glass ceramic; |CT_AV| of the reinforced glass ceramic is ≥ 70MPa, preferably, 70MPa≤|CT_AV|≤110MPa. The reinforced glass ceramic of the present application is (Zn, Mg)Al with high hardness and high modulus. 2 O 4 The crystal phase (solid solution of zinc spinel and magnesium spinel) is the main crystal phase, which gives the reinforced glass ceramics high intrinsic strength or inherent strength. At the same time, the ultra-high compressive stress layer depth and large deep stress of the reinforced glass ceramics of the present application give the reinforced glass ceramics a specific stress structure. Through the synergistic effect of the specific crystal phase structure and the specific stress structure, the reinforced glass ceramics of the present application have ultra-high mechanical strength, especially the reinforced glass ceramics have excellent drop impact resistance.
[0008] In some embodiments of the present application, based on the mass of the reinforced glass-ceramic, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The total content of the crystalline phase is 25.00wt% to 70.00wt%, preferably 30.00wt% to 50.00wt%, wherein (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of the crystalline phase (i.e., (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The mass ratio of the crystalline phase) is 1.00 to 18.00, preferably 1.00 to 15.00; and / or, in the reinforced glass ceramic, (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase is 3.0nm to 10.0nm, preferably 4.0nm to 7.5nm, more preferably 4.5nm to 7.5nm; and / or the strengthened glass-ceramic is transparent in the visible light range. When the total content of the crystalline phase in the strengthened glass-ceramic is W, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of crystal phase (mass ratio Z), (Zn, Mg)Al 2 O 4The average crystal size of the crystalline phase is within the above range, which gives the strengthened glass ceramics a specific crystal phase structure, which is not only conducive to the chemically strengthened glass ceramics obtaining the desired stress structure during chemical strengthening, but also enables the strengthened glass ceramics obtained after strengthening to achieve excellent optical transmittance.
[0009] In some embodiments of the present application, the composition at the center of the reinforced glass-ceramic includes, in terms of molar percentage of oxides: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO 3.00mol%~7.50mol%, ZnO 7.00mol%~13.00mol%, Na 2 O1.00mol%~10.00mol%, Li 2 O 2.50mol%~10.00mol%. The above glass formula is helpful to ensure the preparation of chemically strengthened glass ceramics with high intrinsic strength and spinel as the main crystal phase, which helps to obtain strengthened glass ceramics with desired stress structure.
[0010] In some embodiments of the present application, the reinforced glass-ceramic comprises 15.00 wt% to 45.00 wt% of (Zn, Mg)Al 2 O 4 Crystal phase. (Zn, Mg)Al 2 O 4 The crystal is a crystal with high hardness and high modulus, which is obtained by precipitating an appropriate amount of (Zn, Mg)Al in glass ceramics. 2 O 4 , which can give glass ceramics high intrinsic strength or inherent strength. At the same time, by controlling (Zn, Mg)Al 2 O 4 The content of the crystalline phase makes the glass-ceramics meet a specific crystalline phase structure, which is beneficial to ensure that the glass-ceramics chemically strengthened obtains an ideal stress structure.
[0011] In some embodiments of the present application, take W [(Zn,Mg)Al2O4] (Zn, Mg)Al 2 O 4 The weight percentage of the crystalline phase in the reinforced glass ceramic, W [Al2O3] For Al 2 O 3 The weight percentage of the reinforced glass ceramic is W [MgO]is the weight percentage of MgO in the reinforced glass ceramic, W [ZnO] is the weight percentage of ZnO in the reinforced glass-ceramic,
[0012] A=(1-W [(Zn,Mg)Al2O4] / 2)×W [Al2O3] / 2,
[0013] B=(1-W [(Zn,Mg)Al2O4] )×(W [MgO] +W [ZnO] ),
[0014] C=A / B, in the reinforced glass ceramic, 1.50≤C≤1.85. By optimizing the composition and structure, (Zn, Mg)Al 2 O 4 The crystal content of the crystalline phase, and Al 2 O 3 The contents of MgO and ZnO in the glass ceramics satisfy the range of the above-mentioned characteristic C, which can ensure that the chemically strengthened glass ceramics obtain the desired stress structure after chemical strengthening, thereby enabling the strengthened glass ceramics to obtain high mechanical strength, especially excellent damage resistance.
[0015] In some embodiments of the present application, the value of A is 10.00% to 25.00%, preferably 14.00% to 25.00%; and / or,
[0016] The value of B is 7.50% to 12.50%, preferably 8.00% to 12.00%. By making the values of A and B satisfy the above range, it is helpful to ensure that C satisfies its value range.
[0017] In some embodiments of the present application, the CS_50 of the reinforced glass-ceramic is ≥ 100 MPa, preferably, 100 MPa ≤ CS_50 ≤ 250 MPa. The CS_50 range of the reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic has a high compressive stress at a depth of 50 μm from the surface, indicating that the reinforced glass-ceramic has a high surface stress level.
[0018] In some embodiments of the present application, the Vickers hardness of the reinforced glass-ceramic is greater than or equal to 790 kgf / mm 2 , preferably 790kgf / mm 2 ~1000kgf / mm 2 The Vickers hardness of the reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic has high hardness, thereby ensuring that it has excellent mechanical properties.
[0019] In some embodiments of the present application, the fracture toughness of the reinforced glass-ceramic is greater than or equal to 1.00 MPa·m 1 / 2 , preferably greater than or equal to 1.20 MPa·m 1 / 2 , more preferably greater than or equal to 1.55 MPa·m 1 / 2 , for example, it may be preferably 1.55 MPa·m 1 / 2 ~2.00MPa·m 1 / 2 The fracture toughness of the reinforced glass-ceramic is within the above range, which indicates that the reinforced glass-ceramic has high fracture toughness, thereby ensuring that it has excellent mechanical properties.
[0020] In some embodiments of the present application, the |CT_CV| of the reinforced glass-ceramic is ≥ 80 MPa, preferably, 80 MPa ≤ |CT_CV| ≤ 150 MPa. The |CT_CV| of the reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic has a higher tensile stress level, which in turn reflects that it has a higher surface stress level, thereby ensuring that it has excellent damage resistance.
[0021] In some embodiments of the present application, in the X-ray diffraction spectrum of the strengthened glass ceramic, the peak with the maximum peak intensity in the characteristic peak with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity in the characteristic peak with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak and the second characteristic peak is 0.80 to 1.50, and the peak intensity ratio X is preferably 0.85 to 1.30. In the XRD ray diffraction spectrum, the peak intensity of the characteristic peak can reflect the integrity of the crystal in the glass ceramic. The present application helps to obtain a suitable crystal integrity by making the peak intensity ratio of the above two characteristic peaks within this range, thereby helping to obtain better optical effects and strengthening effects.
[0022] In some embodiments of the present application, in the X-ray diffraction pattern of the reinforced glass-ceramic, the (Zn, Mg)Al 2 O 4 The characteristic peak of the
[400] crystal face of the crystalline phase is located in the range of 2θ angle of 44° to 46°. 2 O 4 The characteristic peak of the
[311] crystal plane of the crystalline phase is located in the range of 2θ angle of 34° to 38°. 2 O 4 The characteristic peak of the
[440] crystal plane of the crystalline phase is located in the 2θ angle range of 64° to 67°;
[0023] The half-peak width W of the characteristic peak of the
[400] crystal plane is
[400] 0.650°~1.800°, preferably W
[400] 0.900° to 1.600°;
[0024] The half-peak width W of the characteristic peak of the
[311] crystal plane is
[311] 0.900°~2.800°, preferably W
[311] 1.100° to 2.230°;
[0025] The half-peak width W of the characteristic peak of the
[440] crystal plane is
[440] 0.750°~2.000°, preferably W
[440] In the present application, the half-peak widths of the characteristic peaks of the
[400] crystal plane, the
[311] crystal plane, and the
[440] crystal plane can reflect the (Zn, Mg)Al 2 O 4 The crystal size, by satisfying the above range, is conducive to ensuring that the chemically strengthened glass-ceramics have a specific crystal size and crystal phase structure, which in turn helps to ensure that the strengthened glass-ceramics obtain the desired optical properties and stress levels.
[0026] In some embodiments of the present application, the composition at the center of the reinforced glass-ceramic further includes, in terms of molar percentage of oxides: K 2 O 0.00mol%~5.00mol%, CaO 0.00mol%~10.00mol%, B 2 O 3 0.00mol%~10.00mol%, BaO 0.00mol%~5.00mol%. In the glass system of the present application, K 2 O, CaO, B 2 O 3 Or BaO as an optional component, the use of an appropriate amount can have a certain improvement effect on the forming effect, crystallization effect, chemical strengthening effect or optical effect of glass ceramics.
[0027] In some embodiments of the present application, the composition at the center of the reinforced glass-ceramic includes, in terms of molar percentage of oxides: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na 2 O2.00mol%~10.00mol%, Li 2O 3.00 mol% to 10.00 mol%. By adjusting the appropriate amount of MgO, ZnO, Li 2 O or Na 2 The content of O helps to ensure that the main crystalline phase content in the chemically strengthened glass-ceramics meets the desired level, and also helps to ensure that the chemically strengthened glass-ceramics achieve the desired chemical strengthening effect, thereby obtaining strengthened glass-ceramics with a high stress level.
[0028] In some embodiments of the present application, the composition at the center of the reinforced glass-ceramic includes, in terms of molar percentage of oxides: SiO 2 35.00mol%~50.00mol%, Al 2 O 3 25.00mol%~35.00mol%, ZrO 2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na 2 O2.00mol%~10.00mol%, Li 2 O 3.00 mol% to 10.00 mol%. By properly adjusting the content of each necessary oxide, it is helpful to ensure that the chemically strengthened glass-ceramics realizes the desired crystal phase structure and glass network structure that can achieve a high stress level, thereby facilitating the acquisition of strengthened glass-ceramics with a high stress level.
[0029] In some embodiments of the present application, based on the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies:
[0030] 1.30≤ZnO / MgO≤2.50; and / or,
[0031] 0.05≤Li 2 O / (Al 2 O 3 -(MgO+ZnO)+SiO 2 )≤0.20; and / or,
[0032] 0.19≤(Al 2 O 3 -(MgO+ZnO)) / SiO 2 ≤0.60; and / or,
[0033] 0.26≤Na 2 O / Li 2 O≤3.00.
[0034] In some embodiments of the present application, the composition at the center of the reinforced glass-ceramic further satisfies, based on the molar percentage of each oxide in the reinforced glass-ceramic composition:
[0035] 12.00mol%≤ZnO+MgO≤20.00mol%, preferably, 13.00mol%≤ZnO+MgO≤17.30mol%; and / or,
[0036] 9.00mol%≤Al 2 O 3 - (MgO + ZnO) ≤ 22.00 mol%, preferably, 10.00 mol% ≤ Al 2 O 3 - (MgO + ZnO) ≤ 20.00 mol%; and / or,
[0037] 5.00mol%≤Na 2 O+Li 2 O≤15.00mol%, preferably, 6.00mol%≤Na 2 O+Li 2 O≤13.50mol%.
[0038] In some embodiments of the present application, the transmittance of the 0.7 mm thick reinforced glass ceramic at 550 nm wavelength is greater than or equal to 85.00%. The transmittance of the 0.7 mm thick reinforced glass ceramic at 550 nm wavelength is within the above range, indicating that the reinforced glass ceramic of the present application has high light transmittance. At the same time, the reinforced glass ceramic of the present application also has high mechanical strength, especially excellent drop impact resistance, which effectively broadens the application scenarios and application fields of the reinforced glass ceramic of the present application.
[0039] In some embodiments of the present application, the 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-grit sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m, preferably the average sandpaper drop resistance height is greater than or equal to 1.40 m, and more preferably 1.50 m to 2.50 m. The average sandpaper drop resistance height H of the 0.7 mm thick reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic of the present application has excellent drop impact resistance.
[0040] In some embodiments of the present application, the reinforced glass-ceramic is obtained by chemically strengthening a chemically strengthened glass-ceramic, and the composition of the chemically strengthened glass-ceramic is the same as the composition at the center of the reinforced glass-ceramic.
[0041] In a second aspect, a glass device is provided, which is made of the reinforced glass ceramic in any of the aforementioned embodiments.
[0042] In a third aspect, an electronic device is provided, comprising the reinforced glass ceramic according to any of the aforementioned embodiments.
[0043] In some embodiments of the present application, the electronic device includes at least one of a mobile phone, a tablet computer, a smart wearable, a display, and a television.
[0044] One or more technical solutions of the present application have the following advantages or beneficial effects:
[0045] The present application provides a reinforced glass ceramic with high strength and its application. The reinforced glass ceramic of the present application is (Zn, Mg)Al with high hardness and high modulus. 2 O 4 The crystal phase (solid solution of zinc spinel and magnesium spinel) is the main crystal phase, which gives the reinforced glass ceramics high intrinsic strength or inherent strength. At the same time, the ultra-high compressive stress layer depth and large deep stress of the reinforced glass ceramics of the present application give the reinforced glass ceramics a specific stress structure. Through the synergistic effect of the specific crystal phase structure and the specific stress structure, the reinforced glass ceramics of the present application have ultra-high mechanical strength and high damage resistance, especially the reinforced glass ceramics have excellent drop impact resistance.
[0046] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0048] Figure 1 Schematic diagram of the structure of the strengthened glass ceramic in some embodiments of the present application, wherein t is the thickness of the glass, d is the depth of the compressive stress layer, 11 is the compressive stress layer, and 12 is the tensile stress layer;
[0049] Figure 2 It is a comparison diagram of the XRD diffraction patterns of the chemically strengthened glass ceramics in Examples 1 to 2 and Comparative Examples 6 to 9;
[0050] Figure 3 is the XRD diffraction pattern of the chemically strengthened glass-ceramic in Comparative Example 8;
[0051] Figure 4 is the XRD diffraction pattern of the chemically strengthened glass-ceramic in Example 2;
[0052] Figure 5 is the XRD diffraction pattern of the chemically strengthened glass-ceramic in Comparative Example 10;
[0053] Figure 6 is the XRD diffraction pattern of the chemically strengthened glass-ceramic in Comparative Example 11;
[0054] Figure 7 is the transmittance curve of the chemically strengthened glass ceramic in Example 1 under different wavelength conditions;
[0055] Figure 8 The XRD diffraction comparison diagram of the chemically strengthened glass ceramic in Example 1 before and after chemical strengthening;
[0056] Fig. 9 This is a comparison chart of the transmittance curves of the chemically strengthened glass ceramic in Example 1 under different wavelength conditions before and after chemical strengthening. DETAILED DESCRIPTION
[0057] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0058] Explanation of terms
[0059] DOL_0: Depth of compressive stress layer, also known as depth of compressive stress layer, refers to the distance along the thickness direction from any surface of the strengthened glass-ceramic to the position where the compressive stress near the surface is zero.
[0060] |CT_AV|: refers to the absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0061] The composition at the center of the strengthened glass-ceramic refers to the composition at the center of the depth of the strengthened glass-ceramic or close to the center of the depth.
[0062] CS_50: refers to the compressive stress value at a depth of 50μm from the surface of the strengthened glass-ceramic along the thickness direction.
[0063] |CT_CV|: refers to the absolute value of the maximum tensile stress in the tensile stress layer, specifically refers to the absolute value of the maximum value of all tensile stresses in the tensile stress layer.
[0064] Base glass: refers to glass that has not been nucleated, crystallized or strengthened.
[0065] Crystalline phase content: the percentage of the mass of the crystal phase in the glass-ceramic to the total mass of the glass-ceramic.
[0066] Peak intensity: refers to the height of the diffraction peak in the XRD spectrum.
[0067] Half-peak width: refers to the width of the half-peak height of the diffraction peak in the XRD spectrum, usually expressed as an angle or 2θ value.
[0068] In the present application, the chemically strengthened glass-ceramic refers to a glass-ceramic material that can be used for chemical strengthening treatment to prepare strengthened glass-ceramic.
[0069] Glass ceramics: also known as microcrystalline glass, is a type of solid composite material that contains both a glass phase and a microcrystalline phase (or also called a crystal phase, a crystalline phase, or a crystalline phase).
[0070] Theoretically, when the depths of the compressive stress layers extending inward from the two main surfaces of the glass product are equal or approximately equal, and the sum of the depths of the two compressive stress layers is equal to the thickness of the tensile stress layer, that is, Figure 1 As shown, the depth d of the compressive stress layer 11 on both sides is approximately equal to 25% of the thickness t of the glass 10, and the thickness of the tensile stress layer 12 is approximately equal to 50% of the thickness t of the glass 10, and the glass will reach the ideal compressive stress layer depth. But in fact, in the prior art, almost no glass products have achieved this target effect. On the one hand, this compressive stress layer depth is relatively difficult to achieve. On the other hand, in the existing glass products, a higher compressive stress layer depth is often accompanied by a decrease in the surface stress level and a decrease in the overall strength of the glass products. Because in the ion exchange process of chemical strengthening treatment, the diffusion of ions becomes more difficult as they go deeper, and simply increasing the diffusion amount by adding alkali metal ions is very likely to cause bursting and fragmentation problems due to excessive internal stress before reaching a higher depth. In addition, for many glass products, after the exchange ion diffusion reaches a certain depth and the stress reaches a certain level, stress relaxation will occur, the depth will increase slightly or not increase, but the stress will decrease significantly, resulting in a decrease in the strength of the glass products. Therefore, at present, the compressive stress depth of glass products can only be made as close to this ideal effect as possible.
[0071] In view of this, a reinforced glass ceramic having an ultra-high compressive stress layer depth and a large deep stress and its application are provided. Through the synergistic effect of a specific crystal phase structure and a specific stress structure, the reinforced glass ceramic of the present application has ultra-high mechanical strength and high damage resistance, and in particular, the reinforced glass ceramic has excellent drop impact resistance.
[0072] In some embodiments of the present application, a strengthened glass-ceramic is provided, wherein the strengthened glass-ceramic comprises a main crystalline phase (Zn, Mg)Al 2 O 4 Crystalline phase and minor crystal phase tetragonal ZrO 2Crystalline phase. The reinforced glass-ceramic includes a compressive stress layer region extending from the surface of the reinforced glass-ceramic to the compression depth, and has a tensile stress layer region inside the reinforced glass-ceramic. The depth of the compressive stress layer DOL_0 of the reinforced glass-ceramic is ≥0.21t, preferably, 0.21t≤DOL_0≤0.25t, and t is the thickness of the reinforced glass-ceramic. In some embodiments, in the reinforced glass-ceramic, DOL_0 may be 0.21t to 0.24t, 0.22t to 0.24t, 0.23t to 0.24t or 0.21t to 0.23t. In some embodiments, DOL_0 may be 0.21t, 0.22t, 0.23t, 0.24t or 0.25t, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, when the thickness t of the reinforced glass-ceramic is 0.7 mm, 147 μm ≤ DOL_0 ≤ 175 μm, specifically, DOL_0 can be 147 μm, 154 μm, 161 μm, 168 μm or 175 μm, or a value within a numerical range consisting of any two of the above values as endpoints. The |CT_AV| of the reinforced glass-ceramic is ≥ 70 MPa, preferably, 70 MPa ≤ |CT_AV| ≤ 110 MPa. In some embodiments, in the reinforced glass-ceramic, |CT_AV| can be 73 MPa to 108 MPa, 75 MPa to 105 MPa, 78 MPa to 100 MPa, 80 MPa to 98 MPa or 83 MPa to 95 MPa. In some embodiments, |CT_AV| may be 70 MPa, 73 MPa, 75 MPa, 78 MPa, 80 MPa, 83 MPa, 85 MPa, 88 MPa, 90 MPa, 93 MPa, 95 MPa, 98 MPa, 100 MPa, 103 MPa, 105 MPa, 108 MPa or 110 MPa, or a value within a range of values formed by taking any two of the above values as endpoints. 2 O 4 The crystalline reinforced glass-ceramics have an ultra-high compressive stress layer depth and a large tensile stress level, which can give the reinforced glass-ceramics high mechanical strength, which is beneficial to greatly improve the damage resistance of the reinforced glass-ceramics, especially to improve the drop impact resistance of the reinforced glass-ceramics.
[0073] The present application has no particular limitation on the thickness t of the reinforced glass-ceramic, as long as the purpose of the present application can be achieved. Exemplarily, the thickness t of the reinforced glass-ceramic satisfies: 0.2 mm ≤ t ≤ 5 mm, preferably 0.2 mm ≤ t ≤ 2 mm.
[0074] In some embodiments of the present application, based on the mass of the reinforced glass-ceramic, (Zn, Mg)Al 2 O 4Crystalline phase and tetragonal ZrO 2 The total content W of the crystalline phase is 25.00wt% to 70.00wt%, preferably 30.00wt% to 50.00wt%, wherein (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of crystal phase (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The mass ratio Z of the crystalline phase is 1.00 to 18.00, preferably 1.00 to 15.00. In some embodiments of the present application, in the above-mentioned strengthened glass ceramics, (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase is 3.0 nm to 10.0 nm, preferably 4.0 nm to 7.5 nm, and more preferably 4.5 nm to 7.5 nm. In some embodiments of the present application, the reinforced glass ceramic is transparent in the visible light range. In the present application, the wavelength range of visible light is 380 nm to 780 nm, and "transparent in the visible light range" means that the transmittance to visible light is greater than 80%.
[0075] For the main crystal phase (Zn, Mg)Al 2 O 4 Crystalline phase and minor crystal phase tetragonal ZrO 2 For spinel glass ceramics with a crystalline phase, simply increasing and introducing the absolute number and type of metal ions that can be ion-exchanged cannot ensure the realization of ultra-high stress layer depth and deep stress. + and Na + When the content exceeds a certain amount, the problem of not being able to obtain transparent glass ceramics may easily arise; on the other hand, the stress distribution of glass ceramics after chemical strengthening is affected by the composition and crystal structure of the glass ceramics. Simply increasing the absolute number and type of alkali metal ions that can be exchanged will not only cause changes in the composition of the glass ceramics, but also cannot guarantee that the glass ceramics will obtain a crystal structure that can achieve the desired stress distribution.
[0076] Without being limited by theory, the composition and crystal structure of glass ceramics are closely related to the stress distribution or stress structure after chemical strengthening. By making the glass ceramics meet the above-mentioned specific composition and crystal structure, it can be ensured that after chemical strengthening, the glass ceramics will obtain an ultra-high compressive stress layer depth and a large deep stress.
[0077] In some embodiments of the present application, based on the mass of the reinforced glass-ceramic, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO2 The total crystalline phase content W of the crystalline phase can be 25.00wt%, 28.00wt%, 30.00wt%, 33.00wt%, 35.00wt%, 38.00wt%, 40.00wt%, 43.00wt%, 45.00wt%, 48.00wt%, 50.00wt%, 53.00wt%, 55.00wt%, 58.00wt%, 60.00wt%, 63.00wt%, 65.00wt%, 68.00wt% or 70.00wt%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, based on the weight of the reinforced glass-ceramic, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The total crystalline content W of the crystalline phase can be 25.00wt% to 68.00wt%, 28.00wt% to 65.00wt%, 32.00wt% to 60.00wt%, 35.00wt% to 55.00wt% or 40.00wt% to 50.00wt%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0078] In some embodiments of the present application, in the above-mentioned strengthened glass-ceramics, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of the crystalline phase (mass ratio Z) can be 1.00, 2.00, 3.00, 4.00, 5.00, 6.00, 7.00, 8.00, 9.00, 10.00, 11.00, 12.00, 13.00, 14.00, 15.00, 16.00, 17.00 or 18.00, or a value within a range of values consisting of any two of the above values as endpoints. In some embodiments, in the above-mentioned strengthened glass-ceramics, (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of the crystalline phase (mass ratio Z) may be 2.00-17.00, 4.00-15.00, 6.00-12.00 or 8.00-10.00. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the reinforced glass-ceramic with the desired properties of the present application can be obtained.
[0079] In some embodiments of the present application, in the above-mentioned strengthened glass-ceramics, (Zn, Mg)Al 2 O 4The average crystal size of the crystalline phase may be 3.0 nm, 4.0 nm, 4.2 nm, 4.5 nm, 4.8 nm, 5.0 nm, 5.2 nm, 5.5 nm, 5.8 nm, 6.0 nm, 6.2 nm, 6.5 nm, 6.8 nm, 7.0 nm, 7.2 nm, 7.5 nm, 8.0 nm, 9.0 nm or 10.0 nm, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, in the above-mentioned strengthened glass-ceramics, (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase can be 4.0nm to 9.0nm, 4.0nmnm to 7.5nm, 4.5nmnm to 7.5nm, 5.0nm to 8.0nm or 6.0nm to 7.0nm. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0080] In some embodiments of the present application, the reinforced glass-ceramic comprises 15.00 wt% to 45.00 wt% of (Zn, Mg)Al 2 O 4 Crystal phase. (Zn, Mg)Al 2 O 4 The crystal is a crystal with high hardness and high modulus, which is obtained by precipitating an appropriate amount of (Zn, Mg)Al in glass ceramics. 2 O 4 , which can give glass ceramics high intrinsic strength or inherent strength. At the same time, by controlling (Zn, Mg)Al 2 O 4 The content of the crystalline phase makes the glass ceramic meet a specific crystalline phase structure, which is conducive to ensuring that the glass ceramic chemical strengthening obtains an ideal stress structure. In some embodiments of the present application, the (Zn, Mg)Al 2 O 4 Crystal content W of the crystal phase [(Zn,Mg)Al2O4] The content of (Zn, Mg) in the strengthened glass-ceramic may be 15.00 wt%, 18.00 wt%, 20.00 wt%, 23.00 wt%, 25.00 wt%, 28.00 wt%, 30.00 wt%, 33.00 wt%, 35.00 wt%, 38.00 wt%, 40.00 wt%, 43.00 wt% or 45.00 wt%, or a value within a range of values consisting of any two of the above values as endpoints. 2 O 4 Crystal content W of the crystal phase [(Zn,Mg)Al2O4]It may be 18.00 wt% to 44.00 wt%, 20.00 wt% to 42.00 wt%, 24.00 wt% to 40.00 wt%, 28.00 wt% to 38.00 wt% or 30.00 wt% to 35.00 wt%.
[0081] In some embodiments of the present application, based on the quality of the strengthened glass-ceramic, tetragonal ZrO 2 Crystal content W of the crystal phase [ZrO2] 2.00wt%~16.00wt%. Tetragonal ZrO 2 Crystalline phase and (Zn, Mg)Al 2 O 4 The crystal phase determines the crystal phase structure inside the glass ceramic. By meeting a specific content range, it is beneficial to ensure the structural strength of the glass ceramic and to ensure that the glass ceramic obtains an ideal stress structure after chemical strengthening. 2 Crystal content W of the crystal phase [ZrO2] It can be 2.00wt%, 3.00wt%, 4.00wt%, 5.00wt%, 6.00wt%, 7.00wt%, 8.00wt%, 9.00wt%, 10.00wt%, 11.00wt%, 12.00wt%, 13.00wt%, 14.00wt%, 15.00wt% or 16.00wt%, or a value within the numerical range formed by taking any two of the above values as endpoints.
[0082] In some embodiments of the present application, the composition at the center of the strengthened glass-ceramic includes, in terms of molar percentage of oxides: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO 3.00mol%~7.50mol%, ZnO 7.00mol%~13.00mol%, Na 2 O1.00mol%~10.00mol%, Li 2 O 2.50mol%~10.00mol%. By adopting this glass formula, it is beneficial to ensure the preparation of chemically strengthened glass-ceramics that meet high intrinsic strength and have spinel as the main crystal phase, which is helpful to obtain strengthened glass-ceramics that meet the desired stress structure.
[0083] It should be understood that after chemical strengthening and ion exchange, the composition of the glass ceramic product at the surface may be different from the composition of the glass ceramic before the ion exchange process. This is because, when ion exchange is performed, a type of alkali metal ion (e.g., Li+) at the surface of the newly formed glass ceramic (e.g., the chemically strengthened glass ceramic in the present application) is + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ). However, in the embodiment, the glass composition and phase assembly at or near the depth center of the glass ceramic product will still be the same as the composition of the newly formed glass ceramic. That is, in the present application, the composition and phase assembly at the center of the chemically strengthened strengthened glass ceramic are the same as those of the newly formed glass ceramic (e.g., the chemically strengthened glass ceramic in the present application).
[0084] Meanwhile, the chemically strengthened glass-ceramic in the present application is prepared by heat-treating the substrate glass, and therefore, based on the molar percentage of the oxides, the composition of the chemically strengthened glass-ceramic is the same as that of the substrate glass. That is, in the present application, the composition of the substrate glass or the chemically strengthened glass-ceramic for preparing the chemically strengthened glass-ceramic, based on the molar percentage of the oxides, includes: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO 3.00mol%~7.50mol%, ZnO 7.00mol%~13.00mol%, Na 2 O1.00mol%~10.00mol%, Li 2 O 2.50mol% to 10.00mol%. After heat treatment of the substrate glass satisfying the above range to obtain a chemically strengthened glass ceramic satisfying a specific crystal phase structure, the chemically strengthened glass ceramic can obtain a strengthened glass ceramic having an ultra-high compressive stress layer depth and a large deep stress through chemical strengthening.
[0085] In the glass system of this application, SiO 2 It is a glass network forming oxide and an indispensable component of the glass network structure. 2 It can increase the stability and mechanical strength of the glass while taking into account the formability of the glass. In the present application, in terms of mol% of oxide, in the composition of the substrate glass or chemically strengthened glass ceramic or strengthened glass ceramic at the center, SiO 2The content of SiO is 35.00 mol% to 60.00 mol%. In some embodiments of the present application, SiO 2 The content of SiO can be 35.00 mol%, 37.00 mol%, 40.00 mol%, 42.00 mol%, 45.00 mol%, 47.00 mol%, 50.00 mol%, 52.00 mol%, 55.00 mol%, 57.00 mol% or 60.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, SiO 2 The content of can be 36.00mol% to 58.00mol%, 38.00mol% to 55.00mol%, 40.00mol% to 52.00mol%, 42.00mol% to 50.00mol% or 44.00mol% to 48.00mol%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0086] In the glass system of this application, an appropriate amount of Al 2 O 3 It can promote the precipitation of the main crystalline phase, inhibit the precipitation of other impurities such as quartz, and avoid the problem of easy crystallization and devitrification of glass during normal cooling due to fast crystallization rate. At the same time, it is beneficial to increase the rate of ion exchange during strengthening and improve the stress structure. In this application, in terms of mol% of oxide, in the composition at the center of the substrate glass or chemically strengthened glass-ceramic or strengthened glass-ceramic, Al 2 O 3 The content of Al is 20.00 mol% to 40.00 mol%. In some embodiments of the present application, 2 O 3 The content of Al may be 20.00 mol%, 21.00 mol%, 22.00 mol%, 23.00 mol%, 24.00 mol%, 25.00 mol%, 26.00 mol%, 27.00 mol%, 28.00 mol%, 29.00 mol%, 30.00 mol%, 31.00 mol%, 32.00 mol%, 33.00 mol%, 34.00 mol%, 35.00 mol%, 36.00 mol%, 37.00 mol%, 38.00 mol%, 39.00 mol% or 40.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, Al 2 O 3The content of may be 21.00mol% to 38.00mol%, 22.00mol% to 36.00mol%, 23.00mol% to 34.00mol% or 25.00mol% to 32.00mol%. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the reinforced glass-ceramic with the desired properties of the present application can be obtained.
[0087] In the glass system of this application, ZrO 2 As an effective nucleating agent, ZrO 2 It first precipitates in the substrate glass in the form of crystals, ZrO 2 The crystal becomes the crystal nucleus for the subsequent growth of the main crystal phase. 2 It is beneficial to form spinel glass ceramics with a specific crystal phase structure. In the present application, in terms of mol% of oxides, in the composition at the center of the base glass or chemically strengthened glass ceramic or strengthened glass ceramic, ZrO 2 The content of ZrO is 2.00 mol% to 8.00 mol%. In some embodiments of the present application, ZrO 2 The content of ZrO can be 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol% or 8.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, ZrO 2 The content of can be 2.50mol% to 7.80mol%, 3.00mol% to 7.50mol%, 3.50mol% to 7.00mol%, 4.00mol% to 6.50mol% or 4.50mol% to 6.00mol%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0088] In the glass system of the present application, MgO and ZnO are necessary components of the main crystalline phase spinel. An appropriate amount of MgO and ZnO is conducive to ensuring the formation of the desired content of the main crystalline phase, and can also reduce the difficulty of melting the substrate glass to a certain extent. However, excessive MgO and ZnO can easily lead to excessive growth of spinel grains, making it difficult to obtain chemically strengthened glass ceramics with high transparency. In the present application, in the composition at the center of the substrate glass or chemically strengthened glass ceramics or strengthened glass ceramics, the content of MgO is 3.00mol% to 7.50mol%, and the content of ZnO is 7.00mol% to 13.00mol%, calculated as mol% of the oxide.
[0089] In some embodiments of the present application, the content of MgO can be 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol% or 7.50mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the content of MgO can be 3.50mol% to 7.00mol%, 4.00mol% to 6.50mol% or 4.50mol% to 6.00mol%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0090] In some embodiments of the present application, the content of ZnO can be 7.00mol%, 7.50mol%, 8.00mol%, 8.50mol%, 9.00mol%, 9.50mol%, 10.00mol%, 10.50mol%, 11.00mol%, 11.50mol%, 12.00mol%, 12.50mol% or 13.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the content of ZnO can be 7.50mol% to 12.50mol%, 8.50mol% to 12.00mol%, 9.50mol% to 11.50mol% or 10.00mol% to 11.00mol%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0091] In the glass system of this application, an appropriate amount of Na 2 O helps glass ceramics obtain high surface compressive stress during chemical strengthening, which is beneficial for glass ceramics to obtain high surface stress levels. 2O can reduce the melting temperature of the substrate glass and the temperature at which crystals are precipitated when the substrate glass is used to prepare chemically strengthened glass ceramics, and can also prevent the substrate glass from being ceramicized during annealing, and prevent the substrate glass from precipitating undesirable impurities when the substrate glass is heat treated to prepare chemically strengthened glass ceramics. In the present application, in terms of mol% of oxides, in the composition at the center of the substrate glass or chemically strengthened glass ceramics or strengthened glass ceramics, Na 2 The content of O is 1.00 mol% to 10.00 mol%. In some embodiments of the present application, Na 2 The content of O can be 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol%, 8.50mol%, 9.00mol%, 9.50mol% or 10.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, Na 2 The content of O can be 1.50 mol% to 9.50 mol%, 2.50 mol% to 8.50 mol%, 3.50 mol% to 7.50 mol%, 4.50 mol% to 6.50 mol% or 5.00 mol% to 6.00 mol%. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0092] In the glass system of this application, an appropriate amount of Li 2 O helps glass ceramics obtain higher deep compressive stress and high compressive stress layer depth in chemical strengthening, which is beneficial for glass ceramics to obtain high deep stress level. 2 O is beneficial to improve the Young's modulus of glass ceramics, and can reduce the melting temperature of the substrate glass and the temperature at which crystals are precipitated when the substrate glass is used to prepare chemically strengthened glass ceramics. It can also avoid ceramicization during the annealing process of the substrate glass, and avoid the precipitation of undesirable impurities or excessive crystal growth during the heat treatment of the substrate glass to prepare chemically strengthened glass ceramics. 2 Too low an amount of O may result in a decrease in the deep stress that can be obtained when chemically strengthening the glass-ceramic for chemical strengthening. In the present application, in terms of mol% of oxides, in the composition at the center of the base glass or the chemically strengthened glass-ceramic or the strengthened glass-ceramic, Li 2 The content of O is 2.50 mol% to 10.00 mol%.
[0093] In some embodiments of the present application, Li 2 The content of O may be 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol%, 8.00 mol%, 8.50 mol%, 9.00 mol%, 9.50 mol% or 10.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, Li 2 The content of O may be 3.00 mol% to 9.50 mol%, 4.00 mol% to 8.50 mol%, 5.00 mol% to 7.50 mol% or 6.00 mol% to 7.00 mol%. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the reinforced glass-ceramic with the desired properties of the present application can be obtained.
[0094] In some embodiments of the present application, take W [(Zn,Mg)Al2O4] (Zn, Mg)Al 2 O 4 The weight percentage of the crystal phase in the strengthened glass-ceramic, W [Al2O3] For Al 2 O 3 Weight percentage of reinforced glass ceramics, W [MgO] is the weight percentage of MgO in the reinforced glass ceramic, W [ZnO] is the weight percentage of ZnO in the reinforced glass-ceramic;
[0095] A=(1-W [(Zn,Mg)Al2O4] / 2)×W [Al2O3] / 2,
[0096] B=(1-W [(Zn,Mg)Al2O4] )×(W [MgO] +W [ZnO] ),
[0097] C=A / B, in strengthened glass ceramics, 1.50≤C≤1.85.
[0098] By optimizing the composition and structure, (Zn, Mg)Al 2 O 4 The crystal content of the crystalline phase, and Al 2 O 3 The contents of MgO and ZnO in the glass ceramics satisfy the range of the above-mentioned characteristic C, which can ensure that the chemically strengthened glass ceramics obtain the desired stress structure after chemical strengthening, thereby enabling the strengthened glass ceramics to obtain high mechanical strength, especially excellent damage resistance.
[0099] In some embodiments of the present application, the value of A is 10.00% to 25.00%, preferably 14.00% to 25.00%; and / or, the value of B is 7.50% to 12.50%, preferably 8.00% to 12.00%. By making the values of A and B satisfy the above range, it is helpful to ensure that C satisfies its value range. In some embodiments of the present application, the value of A can be 10.00%, 11.00%, 12.00%, 13.00%, 14.00%, 15.00%, 16.00%, 17.00%, 18.00%, 19.00%, 20.00%, 21.00%, 22.00%, 23.00%, 24.00% or 25.00%, or a value within the numerical range formed by any two of the above values as endpoints. In some embodiments of the present application, the value of B can be 7.50%, 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, 12.00% or 12.50%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0100] In some embodiments of the present application, W [Al2O3] It is 35.00wt%~50.00wt%.
[0101] In some embodiments of the present application, W [MgO] It is 2.50wt%~4.00wt%.
[0102] In some embodiments of the present application, W [ZnO] It is 9.50wt% to 14.50wt%.
[0103] In some embodiments of the present application, the CS_50 of the strengthened glass-ceramic is ≥100MPa, preferably, 100MPa≤CS_50≤250MPa. The range of CS_50 of the strengthened glass-ceramic is within the above range, indicating that the compressive stress of the strengthened glass-ceramic at a depth of 50μm from the surface is high, which further indicates that the strengthened glass-ceramic has a higher surface stress level, thereby effectively improving the damage resistance of the strengthened glass-ceramic. In some embodiments of the present application, the CS_50 of the strengthened glass-ceramic can be 100MPa, 110MPa, 120MPa, 130MPa, 140MPa, 150MPa, 160MPa, 170MPa, 180MPa, 190MPa, 200MPa, 210MPa, 220MPa, 230MPa, 240MPa or 250MPa, or a value within the numerical range consisting of any two of the above values as endpoints. In some embodiments, the CS_50 of the strengthened glass-ceramic may be 110 to 240 MPa, 120 to 230 MPa, 130 to 220 MPa, 140 to 210 MPa, 150 to 200 MPa, 160 to 190 MPa, or 170 to 180 MPa.
[0104] In some embodiments of the present application, the Vickers hardness of the strengthened glass-ceramic is greater than or equal to 790 kgf / mm 2 , preferably 790kgf / mm 2 ~1000kgf / mm 2 The Vickers hardness of the reinforced glass ceramic is within the above range, indicating that the reinforced glass ceramic has high hardness, thereby ensuring that it has excellent mechanical properties, which is conducive to obtaining glass ceramic products with excellent damage resistance. In some embodiments of the present application, the Vickers hardness of the reinforced glass ceramic can be 790 kgf / mm 2 、800kgf / mm 2 、810kgf / mm 2 、820kgf / mm 2 、830kgf / mm 2 、840kgf / mm 2 、850kgf / mm 2 、860kgf / mm 2 、870kgf / mm 2 、880kgf / mm 2 、890kgf / mm 2 、900kgf / mm 2 、910kgf / mm 2 、920kgf / mm 2 、930kgf / mm 2 、940kgf / mm2 、950kgf / mm 2 、960kgf / mm 2 、970kgf / mm 2 、980kgf / mm 2 、990kgf / mm 2 or 1000kgf / mm 2 , or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the Vickers hardness of the above-mentioned strengthened glass-ceramic can be 800kgf / mm 2 ~980kgf / mm 2 、820kgf / mm 2 ~960kgf / mm 2 、840kgf / mm 2 ~940kgf / mm 2 、860kgf / mm 2 ~920kgf / mm 2 or 880kgf / mm 2 ~900kgf / mm 2 .
[0105] In some embodiments of the present application, the fracture toughness of the reinforced glass-ceramic is greater than or equal to 1.00 MPa·m 1 / 2 , preferably greater than or equal to 1.20 MPa·m 1 / 2 , more preferably greater than or equal to 1.55 MPa·m 1 / 2 , for example, it may be preferably 1.55 MPa·m 1 / 2 ~2.00MPa·m 1 / 2 The fracture toughness of the reinforced glass ceramic is within the above range, indicating that the reinforced glass ceramic has high fracture toughness, thereby ensuring that it has excellent mechanical properties, which is conducive to obtaining glass ceramic products with excellent damage resistance. In some embodiments of the present application, the fracture toughness of the reinforced glass ceramic can be 1.00 MPa·m 1 / 2 , 1.20MPa·m 1 / 2 、1.55MPa·m 1 / 2 , 1.60MPa·m 1 / 2 、1.65MPa·m 1 / 2 , 1.70MPa·m 1 / 2 , 1.75MPa·m 1 / 2 , 1.80MPa·m 1 / 2 、1.85MPa·m 1 / 2 , 1.90MPa·m 1 / 2 , 1.95MPa·m 1 / 2or 2.00MPa·m 1 / 2 , or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the fracture toughness of the above-mentioned reinforced glass-ceramic can be 1.20 MPa·m 1 / 2 ~2.00MPa·m 1 / 2 , 1.40MPa·m 1 / 2 ~1.80MPa·m 1 / 2 or 1.50MPa·m 1 / 2 ~1.90MPa·m 1 / 2 .
[0106] In some embodiments of the present application, the |CT_CV| of the reinforced glass-ceramic is ≥ 80MPa, preferably, 80MPa≤|CT_CV|≤150MPa. The |CT_CV| of the reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic has a higher tensile stress level, which in turn reflects that it has a higher surface stress level, thereby ensuring that it has excellent mechanical properties, which is conducive to obtaining glass-ceramic products with excellent damage resistance. In some embodiments of the present application, the |CT_CV| of the reinforced glass-ceramic can be 80MPa, 85MPa, 90MPa, 95MPa, 100MPa, 105MPa, 110MPa, 115MPa, 120MPa, 125MPa, 130MPa, 135MPa, 140MPa, 145MPa or 150MPa, or a value within the numerical range formed by any two of the above values as endpoints. In some embodiments, the |CT_CV| of the strengthened glass-ceramic may be 85 MPa to 150 MPa, 90 MPa to 145 MPa, 95 MPa to 140 MPa, 100 MPa to 135 MPa, or 110 MPa to 130 MPa.
[0107] The relevant characteristics of the X-ray diffraction spectrum can reflect the crystal structure of the glass ceramic, including crystal composition, crystal size, etc. By making the glass ceramic meet a specific crystal structure, it is beneficial for the glass ceramic to obtain high intrinsic strength on the one hand, and on the other hand, it is beneficial to improve the chemical strengthening effect of the glass ceramic, so that it can obtain ultra-high compressive stress layer depth and large deep stress through chemical strengthening, which is beneficial to improve the mechanical strength and damage resistance of the glass ceramic.
[0108] It should be understood that in the glass ceramics of the present application, the main crystalline phase (Zn, Mg)Al 2 O 4 Crystalline and subcrystalline tetragonal ZrO 2The crystal phase does not contain alkali metal ions, so it does not participate in the ion exchange during the chemical strengthening process. Based on this, the crystal phase structure of the chemically strengthened glass ceramics of the present application is basically the same as that of the chemically strengthened glass ceramics. That is, the crystal phase content, crystal composition, crystal size, and X-ray diffraction spectrum characteristics of the strengthened glass ceramics obtained by the chemical strengthening process of the present application are basically the same as those of the chemically strengthened glass ceramics. Figure 8 As shown, in Example 1, the XRD patterns of the chemically strengthened glass-ceramic before chemical strengthening and the strengthened glass-ceramic after chemical strengthening are substantially the same.
[0109] In some embodiments of the present application, in the X-ray diffraction spectrum of the strengthened glass ceramic, the peak with the maximum peak intensity in the characteristic peak with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity in the characteristic peak with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak and the second characteristic peak is 0.80 to 1.50, and the peak intensity ratio X is preferably 0.85 to 1.30. In the XRD ray diffraction spectrum, the peak intensity of the characteristic peak can reflect the integrity of the crystal in the glass ceramic. The present application helps to obtain a suitable crystal integrity by making the peak intensity ratio of the above two characteristic peaks within this range, thereby helping to obtain better optical effects and strengthening effects. In some embodiments of the present application, the peak intensity ratio X can be 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40 or 1.50, or a value within the numerical range formed by any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired properties of the present application can be obtained.
[0110] In some embodiments of the present application, in the X-ray diffraction pattern of the strengthened glass-ceramic, (Zn, Mg)Al 2 O 4 The characteristic peak of the
[400] crystal plane of the crystalline phase is located in the range of 2θ angle 44°~46°, (Zn, Mg)Al 2 O 4 The characteristic peak of the
[311] crystal plane of the crystalline phase is located in the range of 2θ angle 34°~38°, (Zn, Mg)Al 2 O 4 The characteristic peak of the
[440] crystal face of the crystalline phase is located in the range of 2θ angle 64°~67°, and the half-peak width W of the characteristic peak of the
[400] crystal face is
[400] 0.650°~1.800°, preferably W
[400] 0.900°~1.600°; the half-peak width W of the characteristic peak of the
[311] crystal plane
[311] 0.900°~2.800°, preferably W
[311] 1.100°~2.230°; the half-peak width W of the characteristic peak of the
[440] crystal plane
[440] 0.750°~2.000°, preferably W
[440] In the present application, the half-width of the characteristic peaks of the
[400] crystal plane, the
[311] crystal plane, and the
[440] crystal plane can reflect the size of the crystals in the glass ceramics. By meeting the above ranges, it is helpful to ensure that the chemically strengthened glass ceramics have a specific crystal size and crystal phase structure, which helps to ensure that the strengthened glass ceramics obtain the desired optical properties and stress levels.
[0111] In some embodiments of the present application, W
[400] The value of can be 0.650°, 0.700°, 0.800°, 0.900°, 1.000°, 1.100°, 1.200°, 1.300°, 1.400°, 1.500°, 1.600°, 1.700° or 1.800°, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments of the present application, W
[311] The value of can be 0.900°, 1.000°, 1.100°, 1.200°, 1.300°, 1.400°, 1.500°, 1.600°, 1.700°, 1.800°, 1.900°, 2.000°, 2.100°, 2.200°, 2.230°, 2.300°, 2.400°, 2.500°, 2.600°, 2.700°, or 2.800°, or a numerical value within a numerical range consisting of any two of the above numerical values as endpoints. In some embodiments of the present application, W
[440] The value of can be 0.750°, 0.800°, 0.900°, 1.000°, 1.100°, 1.200°, 1.300°, 1.400°, 1.500°, 1.600°, 1.700°, 1.800°, 1.900° or 2.000°, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0112] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of the oxide, further includes: K 2 O 0.00mol%~5.00mol%, CaO 0.00mol%~10.00mol%, B 2 O 30.00mol%~10.00mol%, BaO 0.00mol%~5.00mol%. In the glass system of the present application, K 2 O, CaO, B 2 O 3 Or BaO as an optional component, the use of an appropriate amount can have a certain improvement effect on the forming effect, crystallization effect, chemical strengthening effect or optical effect of glass ceramics.
[0113] In the glass system of this application, an appropriate amount of K 2 O helps improve the formability of the substrate glass and helps reduce the tendency of the substrate glass to crystallize during the preparation process. In the present application, in terms of mol% of oxides, in the composition at the center of the substrate glass or chemically strengthened glass ceramic or strengthened glass ceramic, K 2 The content of O is 0.00 mol% to 5.00 mol%. In some embodiments of the present application, K 2 O can be 0.00mol%, 0.50mol%, 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol% or 5.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0114] In the glass system of this application, an appropriate amount of B 2 O 3 It helps to reduce the difficulty of melting the substrate glass, helps to promote the precipitation of the main crystal phase spinel, and also helps to effectively avoid the occurrence of opacity or precipitation of impurities that affect the optical properties of glass ceramics when the substrate glass is heat-treated to prepare chemically strengthened glass ceramics. In this application, in terms of mol% of oxides, in the composition at the center of the substrate glass or chemically strengthened glass ceramics or strengthened glass ceramics, B 2 O 3 The content of is 0.00mol% to 10.00mol%. In some embodiments of the present application, B 2 O 3It can be 0.00mol%, 0.50mol%, 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol%, 8.50mol%, 9.00mol%, 9.50mol% or 10.00mol%, or a numerical value within a numerical range consisting of any two of the above numerical values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0115] In the glass system of the present application, an appropriate amount of BaO helps to improve the melting effect of the substrate glass, and can inhibit the growth of grains to a certain extent, thereby improving the optical properties of the glass ceramics to a certain extent. In the present application, in terms of mol% of oxide, in the composition at the center of the substrate glass or chemically strengthened glass ceramics or strengthened glass ceramics, the content of BaO is 0.00mol% to 5.00mol%. In some embodiments of the present application, BaO can be 0.00mol%, 0.50mol%, 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol% or 5.00mol%, or a value within the numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the strengthened glass ceramics with the required performance of the present application can be obtained.
[0116] In the glass system of the present application, an appropriate amount of CaO helps to reduce the viscosity of the glass liquid, improve the formability, strain point and Young's modulus of the glass, and help to improve the ion exchange capacity of the glass ceramic. At the same time, an appropriate amount of CaO helps to improve the gloss and transparency of the glass, helps to reduce the crystallization tendency of the substrate glass, and helps to slow down the hardening speed of the glass. In the present application, in terms of mol% of the oxide, the content of CaO in the composition at the center of the substrate glass or the chemically strengthened glass ceramic or the strengthened glass ceramic is 0.00mol% to 10.00mol%. In some embodiments of the present application, CaO can be 0.00mol%, 0.50mol%, 1.00mol%, 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol%, 8.50mol%, 9.00mol%, 9.50mol% or 10.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0117] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of the oxide, includes: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO3.00mol%~7.50mol%, ZnO 7.00mol%~13.00mol%, Na 2 O 1.00mol%~10.00mol%, Li 2 O2.50mol%~10.00mol%, K 2 O 0.00mol%~5.00mol%, CaO 0.00mol%~10.00mol%, B 2 O 30.00mol%~10.00mol%, BaO 0.00mol%~5.00mol%. The above glass formula is helpful to ensure the preparation of chemically strengthened glass ceramics with high intrinsic strength and spinel as the main crystal phase, which is helpful to obtain strengthened glass ceramics with desired stress structure.
[0118] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of the oxide, includes: SiO 2 35.00mol%~50.00mol%, Al 2 O 3 25.00mol%~35.00mol%, ZrO 2 3.00mol%~5.00mol%, MgO4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na 2 O 2.00mol%~10.00mol%, Li 2 O3.00mol%~10.00mol%, K 2 O 0.00mol%~5.00mol%, CaO 0.00mol%~10.00mol%, B 2 O 3 0.00mol%~10.00mol%, BaO 0.00mol%~5.00mol%. By properly adjusting the content of each necessary oxide, it is helpful to ensure that the chemically strengthened glass-ceramics realizes the desired crystal phase structure and glass network structure that can achieve a high stress level, thereby facilitating the acquisition of strengthened glass-ceramics with a high stress level.
[0119] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of the oxide, includes: SiO 2 35.00mol%~60.00mol%, Al 2 O 3 20.00mol%~40.00mol%, ZrO 2 2.00mol%~8.00mol%, MgO4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na 2 O 2.00mol%~10.00mol%, Li 2O3.00mol%~10.00mol%, K 2 O 0.00mol%~5.00mol%, CaO 0.00mol%~10.00mol%, B 2 O 3 0.00mol%~10.00mol%, BaO 0.00mol%~5.00mol%. By adjusting the appropriate amount of MgO, ZnO, Li 2 O or Na 2 The content of O helps to ensure that the main crystalline phase content in the chemically strengthened glass-ceramics meets the desired level, and also helps to ensure that the chemically strengthened glass-ceramics achieve the desired chemical strengthening effect, thereby obtaining strengthened glass-ceramics with a high stress level.
[0120] In some embodiments of the present application, the composition of the substrate glass or chemically strengthened glass ceramic or the center of the chemically strengthened strengthened glass ceramic, measured by the molar percentage of each oxide in the composition, satisfies: 1.30≤ZnO / MgO≤2.50; by making ZnO and MgO satisfy a specific content relationship, it is beneficial to ensure the formation of the desired main crystalline phase structure. In some embodiments of the present application, the value of ZnO / MgO can be 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40 or 2.50, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the strengthened glass ceramic with the required performance of the present application can be obtained.
[0121] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of each oxide in the composition, satisfies: 0.05≤Li 2 O / (Al 2 O 3 -(MgO+ZnO)+SiO 2 )≤0.20; by making Li 2 O、Al 2 O 3 , MgO, ZnO and SiO 2 Satisfying a specific content relationship helps improve the ion exchange performance of the glass ceramic, helps the glass ceramic obtain a high compressive stress layer depth and a large deep stress through chemical strengthening, and thus helps improve the damage resistance of the strengthened glass ceramic, especially improve its drop impact resistance. 2 O / (Al2 O 3 -(MgO+ZnO)+SiO 2 ) can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.20, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0122] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of each oxide in the composition, satisfies: 0.19≤(Al 2 O 3 -(MgO+ZnO)) / SiO 2 ≤0.60; by making Al 2 O 3 , MgO, ZnO and SiO 2 Satisfying a specific content relationship can ensure that there is an appropriate amount of Al in the residual glass phase of the glass ceramic, which, on the one hand, helps to exert the synergistic effect of Si and Al, so that the residual glass phase forms a specific network structure, thereby improving the intrinsic strength of the glass ceramic, and on the other hand, helps to promote ion exchange and improve the chemical strengthening effect of the glass ceramic. In some embodiments of the present application, (Al 2 O 3 -(MgO+ZnO)) / SiO 2 The value of can be 0.19, 0.20, 0.23, 0.25, 0.28, 0.30, 0.33, 0.35, 0.38, 0.40, 0.43, 0.45, 0.48, 0.50, 0.53, 0.55, 0.58 or 0.60, or a numerical value within a numerical range consisting of any two of the above numerical values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the application can be obtained.
[0123] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of each oxide in the composition, satisfies: 0.26≤Na 2 O / Li 2O≤3.00; by making Na and Li satisfy a specific content relationship, it helps to ensure that the glass ceramic obtains the desired surface stress level and deep stress level after chemical strengthening, thereby obtaining the desired stress structure and achieving high mechanical strength and high damage resistance. 2 O / Li 2 The value of O can be 0.26, 0.30, 0.50, 0.80, 1.00, 1.20, 1.50, 1.80, 2.00, 2.20, 2.30, 2.50, 2.80 or 3.00, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0124] In some embodiments of the present application, the composition at the center of the base glass for preparing chemically strengthened glass-ceramics, or chemically strengthened glass-ceramics, or strengthened glass-ceramics after chemical strengthening, measured by the molar percentage of each oxide in the composition, also satisfies the following: 12.00mol%≤ZnO+MgO≤20.00mol%, preferably, 13.00mol%≤ZnO+MgO≤17.30mol%; by having a sufficient amount of ZnO and MgO in the composition, it helps to ensure that a sufficient amount of main crystalline phase can be precipitated in the glass-ceramics, thereby forming a desired crystalline phase structure. In some embodiments of the present application, the value of ZnO+MgO can be 12.00mol%, 13.00mol%, 13.30mol%, 13.50mol%, 13.80mol%, 14.00mol%, 14.30mol%, 14.50mol%, 14.80mol%, 15.00mol%, 15.30mol%, 15.50mol%, 15.80mol%, 16.00mol%, 16.30mol%, 16.50mol%, 16.80mol%, 17.00mol%, 17.30mol%, 18.00mol%, 19.00mol% or 20.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0125] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of each oxide in the composition, also satisfies: 9.00 mol % ≤ Al 2 O 3- (MgO + ZnO) ≤ 22.00 mol%, preferably, 10.00 mol% ≤ Al 2 O 3 -(MgO+ZnO)≤20.00mol%; by making Al 2 O 3 Higher than the content of MgO and ZnO, while ensuring the formation of the main crystalline phase, it is possible to allow a proper amount of Al to exist in the residual glass phase, which, on the one hand, helps to exert the synergistic effect of Si and Al, so that the residual glass phase forms a specific network structure, thereby improving the intrinsic strength of the glass ceramics, and on the other hand, helps to promote ion exchange and improve the chemical strengthening effect of the glass ceramics. In some embodiments of the present application, Al 2 O 3 The value of -(MgO+ZnO) can be 9.00mol%, 10.00mol%, 11.00mol%, 12.00mol%, 13.00mol%, 14.00mol%, 15.00mol%, 16.00mol%, 17.00mol%, 18.00mol%, 19.00mol%, 20.00mol%, 21.00mol% or 22.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0126] In some embodiments of the present application, the composition of the substrate glass for preparing the chemically strengthened glass-ceramic or the chemically strengthened glass-ceramic or the center of the chemically strengthened strengthened glass-ceramic, in terms of the molar percentage of each oxide in the composition, also satisfies: 5.00mol%≤Na 2 O+Li 2 O≤15.00mol%, preferably, 6.00mol%≤Na 2 O+Li 2 O≤13.50mol%. By having sufficient amounts of Na and Li in the composition, it is helpful to improve the ion exchange performance of the glass ceramic, thereby ensuring that the glass ceramic obtains the desired surface stress level and deep stress level after chemical strengthening, thereby obtaining the desired stress structure and achieving high mechanical strength and high damage resistance. In some embodiments of the present application, Na 2 O+Li 2The value of O can be 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol%, 8.50mol%, 9.00mol%, 9.50mol%, 10.00mol%, 10.50mol%, 11.00mol%, 11.50mol%, 12.00mol%, 12.50mol%, 13.00mol%, 13.50mol%, 14.00mol%, 14.50mol% or 15.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the reinforced glass-ceramic with the desired performance of the present application can be obtained.
[0127] In this application, the above relationship ZnO / MgO, Li 2 O / (Al 2 O 3 -(MgO+ZnO)+SiO 2 )、(Al 2 O 3 -(MgO+ZnO)) / SiO 2 、Na 2 O / Li 2 O, ZnO+MgO, Al 2 O 3 -(MgO+ZnO), Na 2 O+Li 2 Each substance in O represents the molar percentage content of the corresponding substance. For example, ZnO represents the molar percentage content of ZnO, MgO represents the molar percentage content of MgO, etc. This application will not go into details one by one.
[0128] In some embodiments of the present application, the transmittance T of 0.7 mm thick reinforced glass ceramics under 550 nm wavelength light is greater than or equal to 85.00%. The transmittance of 0.7 mm thick reinforced glass ceramics under 550 nm wavelength light is within the above range, indicating that the glass ceramics of the present application have high light transmittance. At the same time, the reinforced glass ceramics of the present application also have excellent damage resistance, especially excellent drop impact resistance, which effectively broadens the application scenarios and application fields of the reinforced glass ceramics of the present application. In some embodiments of the present application, the transmittance T can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, or a value within the numerical range formed by any two of the above values as endpoints. Fig. 9As shown, in the present application, the transmittance of the chemically strengthened glass ceramics is basically the same as the transmittance of the strengthened glass ceramics before and after chemical strengthening. That is to say, in the present application, by adopting chemically strengthened glass ceramics with high transmittance, chemical strengthening treatment can be performed to obtain strengthened glass ceramic products with the same excellent transmittance.
[0129] In some embodiments of the present application, a 0.7 mm thick reinforced glass-ceramic is subjected to an anti-drop test using 80-mesh sandpaper, and the average anti-sandpaper drop height H of the reinforced glass-ceramic is greater than or equal to 1.00 m, preferably the average anti-sandpaper drop height is greater than or equal to 1.40 m, and more preferably 1.50 m to 2.50 m. The average anti-sandpaper drop height H of the 0.7 mm thick reinforced glass-ceramic is within the above range, indicating that the reinforced glass-ceramic of the present application has high mechanical strength and high damage resistance. In some embodiments of the present application, the average anti-sandpaper drop height H can be 1.50 m, 1.60 m, 1.70 m, 1.80 m, 1.90 m, 2.00 m, 2.10 m, 2.20 m, 2.30 m, 2.40 m or 2.50 m, or a value within the numerical range formed by any two of the above values as endpoints.
[0130] In some embodiments of the present application, the strengthened glass-ceramic is obtained by subjecting a chemically strengthened glass-ceramic to a chemically strengthened glass-ceramic, and the composition of the chemically strengthened glass-ceramic is the same as the composition at the center of the strengthened glass-ceramic.
[0131] The preparation method of the reinforced glass-ceramic in any of the aforementioned embodiments of the present application may include but is not limited to the following steps:
[0132] (1) Preparation of substrate glass: Expressed as the molar percentage of oxides, the ingredients are prepared according to the composition at the center of the substrate glass or reinforced glass-ceramic in any of the aforementioned embodiments. After uniform mixing, the substrate glass is prepared by conventional methods known in the art. The substrate glass preparation methods here include but are not limited to float, overflow, rolling, casting, continuous melting and the like. The present application does not limit the various parameters in the preparation process, as long as a transparent substrate glass with the required performance of the present application can be obtained.
[0133] (2) Preparation of chemically strengthened glass ceramics: The base glass obtained in step (1) is subjected to heat treatment, wherein the heat treatment includes but is not limited to a one-step heat treatment or a multi-step heat treatment, to obtain chemically strengthened glass ceramics.
[0134] (3) Chemical strengthening treatment: The chemically strengthened glass ceramic obtained in step (2) is subjected to chemical strengthening treatment to obtain the strengthened glass ceramic in any of the aforementioned embodiments.
[0135] In some embodiments of the present application, the preparation method of the substrate glass in the above step (1) may include but is not limited to the following steps: batching according to the composition at the center of the substrate glass or strengthened glass ceramic in any of the aforementioned embodiments, mixing evenly, melting, molding, cooling, and annealing to obtain the substrate glass. The present application has no special restrictions on the melting temperature and time, as long as each component can be fully melted. Preferably, the melting temperature is 1550℃~1800℃, and the preferred melting time is 3h~12h. The present application does not limit the molding method, as long as the purpose of the present application can be achieved, for example, it can be cast into a molding mold to form a glass brick. The present application does not limit the cooling temperature, as long as the purpose of the present application can be achieved. Preferably, the cooling temperature is 800℃~1000℃. The present application does not limit the annealing temperature and time, as long as the purpose of the present application can be achieved. Preferably, the annealing temperature is 500℃~700℃ and the time is 20h~26h.
[0136] In some embodiments of the present application, the heat treatment in step (2) above includes a nucleation treatment and a crystallization treatment. Preferably, the temperature T of the nucleation treatment is 1 600℃~850℃, more preferably T 1 In some embodiments, the temperature of the nucleation treatment T 1 The temperature may be 600°C, 625°C, 650°C, 675°C, 680°C, 690°C, 700°C, 710°C, 720°C, 725°C, 730°C, 740°C, 750°C, 775°C, 800°C, 825°C or 850°C, or a value within a range of values consisting of any two of the above values as endpoints. Preferably, the nucleation treatment time t 1 0h~72h, more preferably t 1 0h~24h, more preferably t 1 In some embodiments, the nucleation treatment time t 1 It can be 0h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 16h, 24h, 32h, 40h, 48h, 56h, 64h or 72h, or a value within a range of values formed by taking any two of the above values as endpoints. Preferably, the temperature T of the crystallization treatment is 2 In some embodiments, the crystallization temperature T 2The temperature may be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 875°C, 900°C, 925°C, 950°C, 975°C or 1000°C, or a value within a range of values consisting of any two of the above values as endpoints. Preferably, the crystallization treatment time t 2 10min~400min, preferably t 2 In some embodiments, the crystallization treatment time t 2 It can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 150 min, 170 min, 200 min, 220 min, 250 min, 280 min, 300 min, 320 min, 350 min, 370 min or 400 min, or a value within the numerical range formed by taking any two of the above values as endpoints.
[0137] In the present application, when the substrate glass is heat-treated to prepare a chemically strengthened glass-ceramic, a one-step heat treatment may be performed, or a two-step or multi-step heat treatment may be performed. If a one-step heat treatment is performed, it means that the nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, which can be understood as directly performing a crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, is performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed. If a multi-step heat treatment is performed, then the nucleation treatment stage and / or the crystallization treatment stage adopts a step-by-step heating method, that is, the entire heat treatment process will be heated multiple times (more than twice).
[0138] In the present application, the nucleation treatment is to increase the temperature to a specified nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, keep it warm for a certain time, and the holding time here is the nucleation treatment time (also called nucleation time); the crystallization treatment is to increase the temperature to a specified crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, keep it warm for a certain time, and the holding time here is the crystallization treatment time (also called crystallization time).
[0139] In some embodiments of the present application, in step (2), when heat treatment is performed, the heating rate is preferably controlled to be 5K / min to 15K / min, preferably 5K / min to 10K / min. In some embodiments, the heating rate may be 5K / min, 6K / min, 7K / min, 8K / min, 9K / min, 10K / min, 11K / min, 12K / min, 13K / min, 14K / min or 15K / min, or a value within a numerical range consisting of any two of the above values as endpoints.
[0140] In some embodiments of the present application, in step (3), the salt bath for chemical strengthening treatment is a molten salt containing potassium salt and / or sodium salt, the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the sodium salt includes at least one of sodium nitrate, sodium sulfate, and sodium carbonate, preferably sodium nitrate. Preferably, the temperature of the salt bath for chemical strengthening treatment is T 3 380℃~600℃, preferably T 3 400°C to 550°C, preferably T 3 In some embodiments, the temperature of the salt bath for chemical strengthening treatment is T 3 The temperature may be 380°C, 400°C, 425°C, 450°C, 475°C, 500°C, 525°C, 550°C, 575°C or 600°C, or a value within a range of values consisting of any two of the above values as endpoints. 3 1h~48h, preferably t 3 2h~24h, more preferably t 3 In some embodiments, the time of chemical strengthening treatment t 3 The time can be 1h, 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h or 48h, or a value within a range of values formed by any two of the above values as endpoints. By adopting the above chemical strengthening treatment process scheme, the chemically strengthened glass ceramics with specific composition and structure can be strengthened to obtain strengthened glass ceramics with excellent surface stress characteristics and excellent deep stress characteristics, thereby ensuring that the obtained strengthened glass ceramics have high mechanical strength and excellent damage resistance.
[0141] It should be understood that when the chemical strengthening treatment is performed, one step of chemical strengthening treatment may be performed, or two or more steps of chemical strengthening treatment may be performed. In the present application, the temperature of the chemical strengthening treatment is the temperature of the salt bath; when the chemical strengthening treatment includes two or more steps, the time of the chemical strengthening treatment is the sum of the time of each step of the chemical strengthening treatment. In some embodiments of the present application, when the chemical strengthening treatment includes two or more steps, the temperature and time of the chemical strengthening treatment of each step may be the same or different.
[0142] In the present application, the strengthened glass ceramics in any of the above embodiments can be used to produce glass devices with high strength, for example, the glass devices may include but are not limited to worktops, other surfaces, appliance doors, floor tiles, wall panels, storage containers, mobile phone screens, mobile phone back panels, electronic device frames, vehicle windshields, aircraft windshields or aircraft windshields, etc. The strengthened glass ceramics provided in the present application have high mechanical strength and high damage resistance, especially excellent drop impact resistance, so that the glass devices provided in the present application also have excellent mechanical properties.
[0143] In the present application, the reinforced glass ceramic in any of the aforementioned embodiments can be used in electronic devices.
[0144] In some embodiments of the present application, the electronic device includes at least one of a mobile phone, a tablet computer, a smart wearable, a display, and a television. For example, the electronic device may include but is not limited to a mobile phone, a tablet computer, a smart wearable, a display, or a television. Smart wearables may include but are not limited to electronic watches, smart bracelets, smart watches, smart glasses, etc., and displays may include but are not limited to high-definition displays, vehicle-mounted displays, aircraft-mounted displays, etc. Exemplarily, the electronic device may include a housing and an electronic component partially located in the housing, the housing includes a front surface, a rear surface, and a side surface, the electronic component includes a display device, the display device is located at the front surface of the housing or adjacent to the front surface, and the reinforced glass ceramic provided in the present application can be applied to the front surface and / or rear surface and / or side surface of the housing.
[0145] Test method:
[0146] 1. X-ray diffraction (XRD) test
[0147] The sample to be tested was crushed and ground into a sample with a particle size of less than 75 μm. The ground sample was tested using an X-ray diffractometer to obtain an XRD diffraction peak curve and XRD diffraction data. The XRD diffraction data was then analyzed using JADE Standard 8.6 software to obtain the crystalline phase of the sample. The X-ray diffractometer was Shimadzu XRD-6100, the incident angle range used in the test was 2θ=10°~80°, the scanning speed was 6° / min, the operating voltage was 40 kV, and the operating current was 30 mA. Among them, the sample to be tested was a chemically strengthened glass ceramic or a strengthened glass ceramic.
[0148] Average crystal size: The average crystal size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-peak width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the JADEStandard 8.6 software, and Jade outputs the fitting report. According to the angle 2θ value and Peak FWHM value corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), and the crystal size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average crystal size.
[0149] (Zn, Mg)Al 2 O 4 Average crystal size of the crystalline phase: The RAW file (diffraction pattern) output by the XRD instrument was used for phase retrieval and curve fitting in the JADE Standard 8.6 software. In the output fitting report, select (Zn, Mg)Al 2 O 4 The angle 2θ values and Peak FWHM values corresponding to the three diffraction peaks of the crystal phase in the range of 2θ angles of 34° to 38°, 44° to 46°, and 64° to 67° are calculated, and the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), and the crystal sizes of the three diffraction peaks are calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase. Wherein, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-peak width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle.
[0150] Crystalline content: Import the XRD test results (RAW format) into JADE Standard 8.6 software for fitting and calculation to obtain the content of each crystal phase in the glass ceramic, and then calculate the total content of each crystal phase in the glass ceramic. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal phase content of the corresponding crystal phase. Fitting (Zn, Mg)Al 2 O 4 The ratio of the crystalline phase peak area to the total peak area of the fit is (Zn, Mg)Al 2 O 4 Crystal content W of the crystal phase [(Zn,Mg)Al2O4] ; Fitting tetragonal ZrO 2 The ratio of the peak area of the crystalline phase to the total peak area of the fitting is the tetragonal ZrO 2 Crystal content W of the crystal phase [ZrO2] According to W [(Zn,Mg)Al2O4] and W [ZrO2] Calculated (Zn, Mg)Al 2 O 4 Crystalline phase and tetragonal ZrO 2 The ratio of the crystal phase (mass ratio Z) and the total crystal phase content W.
[0151] Peak intensity ratio: Import the XRD test results (RAW format) into JADE Standard 8.6 software and use the peak search function to determine the 2θ position of the peak and the corresponding raw intensity, and calculate the peak intensity ratio, which is the peak intensity ratio X of the first characteristic peak and the second characteristic peak.
[0152] Half-peak width: Import the XRD test results (RAW format) into JADE Standard 8.6 software for phase retrieval and curve fitting. The 2θ position of the peak and the corresponding crystal plane, half-peak width, and fitting intensity are obtained in the output fitting report. Calculate the ratio based on the fitting intensity of the corresponding crystal plane.
[0153] Specifically, the fitting peak intensity I of the characteristic peak of the
[400] crystal plane
[400] , the fitting peak intensity of the characteristic peak of
[311] crystal plane I
[311] ,
[440] The fitting peak intensity of the characteristic peak of the crystal plane I
[440] , the half-peak width W of the characteristic peak of the
[400] crystal plane
[400] 、The half-peak width W of the characteristic peak of the
[311] crystal plane
[311] 、
[440] half-peak width W of the characteristic peak of the crystal plane
[440] ,I
[400] / I
[311] and I
[440] / I
[311] .
[0154] Taking into account the influence of noise in the test process on peak search, the XRD diffraction peak curve can be smoothed no more than three times.
[0155] 2. Tests of |CT_AV|, DOL_0, CS_50, |CT_CV|
[0156] The test was conducted using a stress meter SLP-2000 manufactured by Luceo (Japan Orihara), with a light source wavelength of 518 nm, SOC = 25.5 (nm / cm) / MPa, a refractive index = 1.60, and an exposure time of 300 usec.
[0157] When testing the surfaces CS_50, |CT_AV|, DOL_0, |CT_CV|, it is necessary to first drop a conductive liquid on the stress meter, then wipe the strengthened glass ceramic sample to be tested clean, place it on the test path, and test its stress value. The stress meter is SLP-2000 and the conductive liquid used is a conductive liquid with a refractive index of 1.51.
[0158] 3. Thickness test
[0159] The thickness of chemically strengthened glass ceramics was measured using a micrometer.
[0160] It should be understood that when chemical strengthening treatment is carried out, the degree of ion exchange changes gradually from the surface to the center of the chemically strengthened glass-ceramics in the thickness direction, and the overall Na-K and / or Li-Na exchange amount generally does not exceed 1% of the total mass of the sample, and the difference in ion radius is at the pm (picometer) level, so the expansion effect in the thickness direction is extremely slight, that is, before and after chemical strengthening, the thickness of the chemically strengthened glass-ceramics changes very little, and it can be approximately considered that the thickness has basically not changed.
[0161] 4. Optical performance test
[0162] The sample to be tested is cleaned in an ultrasonic cleaning machine, and the cleaning conditions include: cleaning time: 10 minutes; cleaning agent used: detergent diluted 10 times; cleaning temperature: 55±10℃; cleaning frequency: 30±10KHZ. Then the transmittance of the sample to be tested at different wavelengths is tested using a haze meter, and the test is carried out with reference to the standard "GB / T 7962.12-2010 Test method for colorless optical glass Part 12: spectral transmittance". The haze meter used in this patent is the Japanese Konica Minolta spectrophotometer CM-3600A. Among them, the sample to be tested is chemically strengthened glass ceramics or strengthened glass ceramics.
[0163] 5. Vickers hardness HV test
[0164] A reinforced glass-ceramic with a clean surface and no visible scratches, pits, cracks or other damage was selected as a sample. A digital display small load Vickers hardness tester VTD405 (Beijing Wowei Technology Co., Ltd.) was used to test the Vickers hardness of the reinforced glass-ceramic in accordance with the national standard GB / T 37900-2019 "Ultra-thin glass hardness and fracture toughness test method small load Vickers hardness indentation method". The load was 300gf and the load time was 10s. The effectiveness of the indentation was in accordance with the national standard GB / T 16534-2009 "Fine ceramic room temperature hardness test method". When the Vickers hardness test was performed in this application, a reinforced glass-ceramic sample with a length, width and thickness of 50mm×50mm×0.7mm was tested. Three different locations on the same sample surface were selected for measurement, and the average value was selected as the final test result.
[0165] 6. Surface K 2 O concentration test
[0166] In this application, the surface K of the strengthened glass ceramic 2 The O concentration was measured by X-ray fluorescence spectrometer (XRF). The equipment model used was (Thermo Scientific ARL PERFORM'X), the target material was Rh (rhodium), the light tube voltage was 40kW, the current was 60mA, the collimator was 0.15, the crystal was LiF200, the detector was FPC, the test range was 29mm circle, and the analysis software was UniQuant standardless analysis.
[0167] Strengthened glass ceramic surface K 2 O concentration C = K 2 O mass / total mass of oxides, where oxides include SiO 2 、Al 2 O 3 、ZrO 2 、Na 2 O.K 2 O and other oxides that can be accurately tested by XRF, excluding B 2 O 3 XRF cannot accurately test the content of the oxides obtained. XRF testing uses a standardless test and does not test the concentration of elements with atomic numbers 6 and below or their oxides in the strengthened glass-ceramics. That is, XRF is not very effective in testing the K content of the surface of the strengthened glass-ceramics. 2 When the concentration of O is greater than 20%, the total mass of oxides measured does not include the mass of elements with atomic numbers 6 and below or their oxides in the strengthened glass-ceramics.
[0168] 7. Average sandpaper drop resistance test
[0169] The average sandpaper drop height refers to the sum of the sandpaper drop heights measured for each sample of the same embodiment or the same comparative example, and the ratio of the number of reinforced glass-ceramic samples to the number of reinforced glass-ceramic samples, which can be used to characterize the drop damage resistance of the reinforced glass-ceramic. Ten identical reinforced glass-ceramic samples were taken from each batch for testing, and the average sandpaper drop height was:
[0170]
[0171] Where n is the number of strengthened glass-ceramic samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.
[0172] Among them, the test method for the sandpaper drop height of a single sample is:
[0173] Step 1: Paste 80-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;
[0174] Step 2: Place a 50mm×50mm×0.7mm long, wide and thick reinforced glass-ceramic sample to be tested directly under the model machine, with the reinforced glass-ceramic sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the reinforced glass-ceramic sample directly under the model machine. If the reinforced glass-ceramic sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, increase the height by 0.1m each time and drop again until the reinforced glass-ceramic sample breaks;
[0175] Step 3: The last drop height of the reinforced glass-ceramic sample when it is broken is recorded as the anti-sandpaper drop height. For example, if the drop height when it is broken is 0.5m, then the anti-sandpaper drop height of the sample is 0.4m.
[0176] 8. Density
[0177] This application uses the electronic density balance SD-200L of Japan ALFA MIRAGE to test the density of reinforced glass ceramics. The test principle is "Archimedes drainage method".
[0178] 9. Fracture toughness test
[0179] The test was carried out according to the national standard GB / T 37900-2019 "Ultra-thin glass hardness and fracture toughness test method - small load Vickers hardness indentation method". Specifically, the indentation was prepared in the same way as the Vickers hardness measurement, and the crack length 2C in the diagonal direction of the indentation was measured. 1 , 2C 2, and its maximum value cannot exceed the thickness of the reinforced glass ceramic. At least 5 effective indentation morphology measurements are performed on the surface of one sample, and the average value is calculated as the final result value of the sample.
[0180] Indentation fracture toughness calculation formula:
[0181] IFR: Indentation fracture toughness, unit is MPa·m 1 / 2) ; E: elastic modulus of the sample, in GPa; 2C 1 , 2C 2 : Crack extension length in the diagonal direction of the indentation, in millimeters (mm), d 1 ,d 2 : The diagonal length of the indentation, in millimeters (mm); F: The test load value, in Newton (N).
[0182] In the above test method, the reinforced glass ceramic tiles in the embodiments and comparative examples are shaped, cut and polished to obtain reinforced glass ceramic samples of desired size (e.g., polished sheets), which are then tested, such as glass ceramic polished sheets with a length, width and thickness of 50 mm × 50 mm × 0.7 mm.
[0183] Example 1
[0184] <Preparation of substrate glass>
[0185] According to the formula 1 in Table 1, the raw material formula for glass production was converted into the raw material formula for batching. The total mass of the raw materials was 1000 g, and then mixed with a V-type mixer for 30 minutes. After mixing, 5 g of clarifier NaCl was added, and then transferred to a platinum crucible and melted in a 1650°C lifting furnace (lifting furnace model: SJF1750, manufacturer: Nanjing Boyuntong Instrument Technology Co., Ltd.) for 5 hours, and then poured into a stainless steel mold preheated at 300°C for molding and cooling. It was cooled to 900°C and then placed in a 600°C annealing furnace for annealing for 24 hours. It was then cooled to room temperature with the furnace to obtain the substrate glass.
[0186] <Preparation of Chemically Strengthened Glass Ceramics>
[0187] The substrate glass prepared as above is heat-treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.) to obtain a glass ceramic for chemical strengthening.
[0188] Specifically, the two-step heat treatment process is adopted, firstly the temperature is raised to the nucleation temperature for nucleation treatment, and then the temperature is raised to the crystallization temperature for crystallization treatment; the heating rate during the nucleation treatment and crystallization process is 10K / min. Among them, the nucleation temperature T 1is 740℃, and the nucleation time t 1 The crystallization temperature is 480 min. 2 The temperature is 800℃, and the crystallization time is t 2 For 10 minutes.
[0189] According to the needs, the chemically strengthened glass ceramics are cut, CNC machined (computer numerical control, i.e., numerical control machine tools, the CNC equipment model used in this application is: RCG500S), and polished in sequence to obtain smooth chemically strengthened glass ceramic sheets of the required specifications. In this application, the specifications of the processed chemically strengthened glass ceramic sheets are samples with a length, width, and thickness of 50 mm × 50 mm × 0.7 mm.
[0190] <Preparation of Strengthened Glass-Ceramics>
[0191] The chemically strengthened glass ceramics were placed in 100 wt% NaNO at 450 °C. 3 The first strengthening treatment was carried out in a salt bath for 3 h, and then placed in 100 wt% KNO at 430 °C. 3 The second strengthening treatment is carried out in a salt bath for 2 hours to obtain strengthened glass ceramics.
[0192] Embodiment 2 to Embodiment 8
[0193] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1. The corresponding formula in Table 2 is shown in Table 1.
[0194] Embodiment 9-embodiment 10
[0195] In addition to placing the corresponding chemically strengthened glass-ceramics in 100 wt % NaNO at 450 °C according to Table 5, 3 The process is the same as in Example 1 except that the corresponding reinforced glass ceramics are obtained by placing the mixture in the salt bath for 4 hours.
[0196] Comparative Example 1 to Comparative Example 11
[0197] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1. The corresponding formula in Table 2 is shown in Table 1.
[0198] Comparative Example 12 to Comparative Example 15
[0199] In addition to placing the corresponding chemically strengthened glass-ceramics in 100 wt % NaNO at 450 °C according to Table 5, 3 The process is the same as in Example 1 except that the corresponding reinforced glass ceramics are obtained by placing the mixture in the salt bath for 4 hours.
[0200] The formulations of the embodiments and comparative examples are shown in Table 1, and the preparation parameters and performance tests of the embodiments and comparative examples are shown in Tables 2 to 5.
[0201]
[0202]
[0203]
[0204]
[0205] After testing, the chemically strengthened glass ceramics of Examples 1 to 8 and Comparative Examples 1 to 11 all contain the main crystalline phase (Zn, Mg)Al 2 O 4 Crystalline phase and minor crystal phase tetragonal ZrO 2 Crystal phase, XRD patterns of some embodiments and comparative examples are shown in Figures 2 to 6 , Figure 8 shown.
[0206] Referring to Tables 1 to 4, the DOL_0 and |CT-AV| of the reinforced glass-ceramics of Examples 1 to 8 are within the scope of the present application, while at least one of DOL_0 and |CT-AV| in Comparative Examples 1 to 11 is not within the scope of the present application. The reinforced glass-ceramics in the examples of the present application have higher Vickers hardness, fracture toughness, and higher average sandpaper drop resistance height, indicating that the reinforced glass-ceramics obtained in the examples of the present application have higher mechanical strength. At the same time, the transmittance of the chemically strengthened glass-ceramics in the examples to 550nm wavelength light is above 89.00%, so that the obtained reinforced glass-ceramics also have excellent light transmittance. Specifically, Figure 7 As shown, the transmittance of the chemically strengthened glass ceramic in Example 1 to visible light is 80.00% or more, and the obtained strengthened glass ceramic is transparent in the visible light range.
[0207] Examples 1 to 2 and Comparative Examples 6 to 9 are all chemically strengthened glass ceramics obtained by subjecting the glass substrate of the composition of Formula 1 to different heat treatment regimes. The XRD diffraction patterns thereof are as follows: Figure 2 shown.
[0208] Reference Figure 2 As shown in Table 3, the XRD spectrum of Comparative Example 6 does not have a second characteristic peak with a 2θ angle in the range of 36° to 38°, so it does not have a peak intensity ratio X. The (Zn, Mg)Al 2 O 4The crystalline content is low, the calculation result of formula C does not meet the scope of the present application, and the stress level of the reinforced glass ceramic prepared in comparative example 6 is low. Figure 2 As shown in Table 3, the peak intensity ratio X of the XRD spectrum of Comparative Example 7 is 1.61, and the (Zn, Mg)Al 2 O 4 The crystal phase content is low, the half-peak width of some crystal plane characteristic peaks does not meet the requirements of this application, the calculation result of formula C does not meet the scope of this application, and the stress level of the strengthened glass ceramic prepared in comparative example 7 is also low. Figure 2 , Figure 3 In the XRD spectrum of Comparative Example 8, the 2θ angle has a peak in the range of 28° to 32°. 2 O 4 The crystal phase content is high, (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase is too high, the half-peak width of the characteristic peak of the crystal face does not meet the requirements of this application, and the calculation result of formula C does not meet the scope of the scheme of this application. The stress level of the strengthened glass-ceramic prepared in comparative example 8 is too low. Figure 2 In the XRD spectrum of Comparative Example 9, the 2θ angle has a peak in the range of 28° to 32°. In the chemically strengthened glass ceramic of Comparative Example 9, (Zn, Mg)Al 2 O 4 The crystal phase content is also high, (Zn, Mg)Al 2 O 4 The average crystal size of the crystalline phase is also relatively high, and the calculation result of Formula C does not meet the scope of the present application. The stress level of the reinforced glass-ceramic obtained in Example 9 is also relatively low.
[0209] Comparative Examples 10 and 11 are both chemically strengthened glass ceramics obtained by different heat treatment systems on the substrate glass of the composition of Formula 5. The XRD diffraction patterns thereof are as follows: Figure 5 and Figure 6 shown.
[0210] The XRD pattern of Comparative Example 10 is as follows Figure 5 As shown in FIG. 10 , the 2θ angle has peaks in the range of 28° to 32° and in the range of 36° to 38°. 2 O 4 The average crystal size of the crystalline phase is too high, and the calculation result of formula C does not meet the scope of the present application. The stress level of the reinforced glass-ceramic prepared in comparative example 10 is too low. The XRD spectrum of comparative example 11 is as follows: Figure 6As shown in FIG. 11 , the 2θ angle has a peak in the range of 28° to 32°. 2 O 4 The average crystal size of the crystalline phase is relatively high, the half-width of the characteristic peaks of some crystal planes does not meet the requirements of this application, the peak intensity ratio X does not meet the scope of the scheme of this application, and the calculation result of formula C does not meet the scope of the scheme of this application. The stress level of the strengthened glass-ceramic obtained in Example 11 is relatively low.
[0211] Comparative Examples 12 to 15 and Examples 9 to 10 obtain chemically strengthened glass ceramics by using different heat treatment systems on the substrate glass of the composition of Formula 1. The strengthened glass ceramics obtained using the same chemical strengthening treatment conditions, the compressive stress layer depth DOL-0 of Comparative Examples 12 to 15 are not within the scope of the present application, and their drop impact resistance is worse than that of the examples of the present application.
[0212] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0213] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0214] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A reinforced glass ceramic, characterized in that: The reinforced glass ceramic contains a main crystalline phase (Zn, Mg) Al2O4 crystalline phase and a secondary crystalline phase tetragonal ZrO2 crystalline phase; the reinforced glass ceramic contains a compressive stress layer region extending from the surface of the reinforced glass ceramic to a compression depth, and has a tensile stress layer region inside; the compressive stress layer depth DOL_0 of the reinforced glass ceramic is ≥0.21t, t is the thickness of the reinforced glass ceramic; |CT_AV| of the reinforced glass ceramic is ≥70MPa; The composition at the center of the reinforced glass-ceramic includes, in terms of molar percentage of oxides: SiO2 35.00mol% to 60.00mol%, Al2O3 20.00mol% to 40.00mol%, ZrO2 2.00mol% to 8.00mol%, MgO3.00mol% to 7.50mol%, ZnO 7.00mol% to 13.00mol%, Na2O 1.00mol% to 10.00mol%, Li2O2.50mol% to 10.00mol%; Take W [(Zn,Mg)Al2O4] is the weight percentage of the (Zn, Mg)Al2O4 phase in the strengthened glass ceramic, W [Al2O3] is the weight percentage of Al2O3 in the reinforced glass ceramic, W [MgO] is the weight percentage of MgO in the reinforced glass ceramic, W [ZnO] is the weight percentage of ZnO in the reinforced glass-ceramic, A=(1-W [(Zn,Mg)Al2O4] / 2)×W [Al2O3] / 2, B=(1-W [(Zn,Mg)Al2O4] )×(W [MgO] +W [ZnO] ), C=A / B, in the reinforced glass-ceramic, 1.50≤C≤1.85; and Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 6.82mol%≤Na2O+Li2O≤15.00mol%; 0.26≤Na2O / Li2O≤0.89; and 0.066≤Li2O / (Al2O3-(MgO+ZnO)+SiO2)≤0.
20.
2. The reinforced glass ceramic according to claim 1, characterized in that: The depth of the compressive stress layer of the strengthened glass-ceramic satisfies 0.21t≤DOL_0≤0.25t.
3. The reinforced glass ceramic according to claim 1, characterized in that: The reinforced glass-ceramic satisfies 70MPa≤|CT_AV|≤110MPa.
4. The reinforced glass ceramic according to claim 1, characterized in that: Calculated based on the mass of the reinforced glass-ceramic, the total content of (Zn, Mg)Al2O4 crystal phase and tetragonal ZrO2 crystal phase is 25.00wt%~70.00wt%, wherein the ratio of (Zn, Mg)Al2O4 crystal phase to tetragonal ZrO2 crystal phase is 1.00~18.00; and / or, in the reinforced glass-ceramic, the average crystal size of the (Zn, Mg)Al2O4 crystal phase is 3.0nm~10.0nm; and / or, the reinforced glass-ceramic is transparent in the visible light range.
5. The reinforced glass ceramic according to claim 4, characterized in that: Calculated based on the mass of the reinforced glass-ceramic, the total content of the (Zn, Mg)Al2O4 crystal phase and the tetragonal ZrO2 crystal phase is 30.00wt% to 50.00wt%.
6. The reinforced glass ceramic according to claim 4, characterized in that: In the reinforced glass-ceramics, the ratio of (Zn, Mg)Al2O4 crystal phase to tetragonal ZrO2 crystal phase is 1.00 to 15.
00.
7. The reinforced glass ceramic according to claim 4, characterized in that: In the reinforced glass-ceramic, the average crystal size of the (Zn, Mg)Al2O4 crystal phase is 4.0 nm to 7.5 nm.
8. The reinforced glass ceramic according to claim 7, characterized in that: In the reinforced glass-ceramic, the average crystal size of the (Zn, Mg)Al2O4 crystal phase is 4.5 nm to 7.5 nm.
9. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The reinforced glass-ceramic contains 15.00wt% to 45.00wt% of the (Zn, Mg)Al2O4 crystal phase.
10. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The value of A is 10.00% to 25.00%; and / or, The value of B is 7.50% to 12.50%.
11. The reinforced glass ceramic according to claim 10, characterized in that: The value of A is 14.00% to 25.00%.
12. The reinforced glass ceramic according to claim 10, characterized in that: The value of B is 8.00% to 12.00%.
13. The reinforced glass ceramic according to claim 9, characterized in that: The value of A is 10.00% to 25.00%; and / or the value of B is 7.50% to 12.50%.
14. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The CS_50 of the reinforced glass-ceramic is ≥100MPa.
15. The reinforced glass ceramic according to claim 14, characterized in that: The reinforced glass-ceramic satisfies 100MPa≤CS_50≤250MPa.
16. The reinforced glass ceramic according to claim 9, characterized in that: The CS_50 of the reinforced glass-ceramic is ≥100MPa.
17. The reinforced glass ceramic according to claim 10, characterized in that: The CS_50 of the reinforced glass-ceramic is ≥100MPa.
18. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The Vickers hardness of the reinforced glass ceramic is greater than or equal to 790 kgf / mm 2 .
19. The reinforced glass ceramic according to claim 18, characterized in that: The Vickers hardness of the reinforced glass ceramic is 790 kgf / mm 2 ~1000kgf / mm 2 .
20. The reinforced glass ceramic according to claim 9, characterized in that: The Vickers hardness of the reinforced glass ceramic is greater than or equal to 790 kgf / mm 2 .
21. The reinforced glass ceramic according to claim 10, characterized in that: The Vickers hardness of the reinforced glass ceramic is greater than or equal to 790 kgf / mm 2 .
22. The reinforced glass ceramic according to claim 14, characterized in that: The Vickers hardness of the reinforced glass ceramic is greater than or equal to 790 kgf / mm 2 .
23. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.00 MPa·m 1 / 2 .
24. The reinforced glass ceramic according to claim 23, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.20 MPa·m 1 / 2 .
25. The reinforced glass ceramic according to claim 24, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.55 MPa·m 1 / 2 .
26. The reinforced glass ceramic according to claim 9, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.00 MPa·m 1 / 2 .
27. The reinforced glass ceramic according to claim 10, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.00 MPa·m 1 / 2 .
28. The reinforced glass-ceramic according to claim 14, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.00 MPa·m 1 / 2 .
29. The reinforced glass-ceramic according to claim 18, characterized in that: The fracture toughness of the reinforced glass ceramic is greater than or equal to 1.00 MPa·m 1 / 2 .
30. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
31. The reinforced glass ceramic according to claim 30, characterized in that The reinforced glass ceramic satisfies 80MPa≤|CT_CV|≤150MPa.
32. The reinforced glass ceramic according to claim 9, characterized in that: The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
33. The reinforced glass ceramic according to claim 10, characterized in that: The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
34. The reinforced glass-ceramic according to claim 14, characterized in that: The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
35. The reinforced glass-ceramic according to claim 18, characterized in that: The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
36. The reinforced glass-ceramic according to claim 23, characterized in that: The |CT_CV| of the reinforced glass-ceramic is ≥80MPa.
37. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
38. The reinforced glass ceramic according to claim 37, characterized in that The peak intensity ratio X between the first characteristic peak and the second characteristic peak is 0.85 to 1.
30.
39. The reinforced glass-ceramic according to claim 9, characterized in that: In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
40. The reinforced glass-ceramic according to claim 10, characterized in that: In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
41. The reinforced glass-ceramic according to claim 14, characterized in that: In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
42. The reinforced glass-ceramic according to claim 18, characterized in that In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
43. The reinforced glass-ceramic according to claim 23, characterized in that: In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
44. The reinforced glass-ceramic according to claim 30, characterized in that In the X-ray diffraction pattern of the strengthened glass-ceramic, the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 28° to 32° is taken as the first characteristic peak, and the peak with the maximum peak intensity among the characteristic peaks with a 2θ angle in the range of 36° to 38° is taken as the second characteristic peak, and the peak intensity ratio X of the first characteristic peak to the second characteristic peak is 0.80 to 1.
50.
45. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
46. The reinforced glass-ceramic according to claim 45, characterized in that The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.900° to 1.600°.
47. The reinforced glass-ceramic according to claim 45, characterized in that The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 1.100° to 2.230°.
48. The reinforced glass-ceramic according to claim 45, characterized in that The half-peak width W of the characteristic peak of the [440] crystal plane is [440] 0.900° to 1.600°.
49. The reinforced glass-ceramic according to claim 9, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
50. The reinforced glass-ceramic according to claim 10, characterized in that: In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
51. The reinforced glass-ceramic according to claim 14, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
52. The reinforced glass-ceramic according to claim 18, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
53. The reinforced glass-ceramic according to claim 23, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
54. The reinforced glass-ceramic according to claim 30, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
55. The reinforced glass-ceramic according to claim 37, characterized in that In the X-ray diffraction spectrum of the strengthened glass-ceramic, the characteristic peak of the [400] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 44° to 46°, the characteristic peak of the [311] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 34° to 38°, and the characteristic peak of the [440] crystal plane of the (Zn, Mg)Al2O4 crystal phase is located at a 2θ angle of 64° to 67°; The half-peak width W of the characteristic peak of the [400] crystal plane is [400] 0.650°~1.800°; The half-peak width W of the characteristic peak of the [311] crystal plane is [311] 0.900°~2.800°; The half-peak width W of the characteristic peak of the [440] crystal plane is [440] It is 0.750°~2.000°.
56. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that Calculated by molar percentage of oxides, the composition at the center of the strengthened glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
57. The reinforced glass-ceramic according to claim 9, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
58. The reinforced glass-ceramic according to claim 10, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
59. The reinforced glass-ceramic according to claim 14, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
60. The reinforced glass-ceramic according to claim 18, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
61. The reinforced glass-ceramic according to claim 23, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
62. The reinforced glass-ceramic according to claim 30, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
63. The reinforced glass-ceramic according to claim 37, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
64. The reinforced glass-ceramic according to claim 45, characterized in that Calculated by molar percentage of oxides, the composition at the center of the reinforced glass-ceramic further includes: K2O 0.00mol%-5.00mol%, CaO 0.00mol%-10.00mol%, B2O3 0.00mol%-10.00mol%, BaO 0.00mol%-5.00mol%.
65. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
66. The reinforced glass-ceramic according to claim 9, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
67. The reinforced glass-ceramic according to claim 10, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
68. The reinforced glass-ceramic according to claim 14, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
69. The reinforced glass-ceramic according to claim 18, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
70. The reinforced glass-ceramic according to claim 23, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
71. The reinforced glass-ceramic according to claim 30, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
72. The reinforced glass-ceramic according to claim 37, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
73. The reinforced glass-ceramic according to claim 45, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
74. The reinforced glass-ceramic according to claim 56, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~60.00mol%, Al2O3 20.00mol%~40.00mol%, ZrO2 2.00mol%~8.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
75. The reinforced glass-ceramic according to any one of claims 1 to 8, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
76. The reinforced glass-ceramic according to claim 9, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
77. The reinforced glass-ceramic according to claim 10, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
78. The reinforced glass-ceramic according to claim 14, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
79. The reinforced glass-ceramic according to claim 18, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
80. The reinforced glass-ceramic according to claim 23, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
81. The reinforced glass-ceramic according to claim 30, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
82. The reinforced glass-ceramic according to claim 37, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
83. The reinforced glass-ceramic according to claim 45, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
84. The reinforced glass-ceramic according to claim 56, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
85. The reinforced glass-ceramic according to claim 65, characterized in that Calculated in molar percentage of oxides, the composition at the center of the reinforced glass-ceramic includes: SiO2 35.00mol%~50.00mol%, Al2O3 25.00mol%~35.00mol%, ZrO2 3.00mol%~5.00mol%, MgO 4.00mol%~7.00mol%, ZnO 9.00mol%~12.00mol%, Na2O 2.00mol%~10.00mol%, and Li2O 3.00mol%~10.00mol%.
86. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
87. The reinforced glass-ceramic according to claim 9, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
88. The reinforced glass-ceramic according to claim 10, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
89. The reinforced glass-ceramic according to claim 14, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
90. The reinforced glass-ceramic according to claim 18, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
91. The reinforced glass-ceramic according to claim 23, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
92. The reinforced glass-ceramic according to claim 30, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
93. The reinforced glass-ceramic according to claim 37, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
94. The reinforced glass-ceramic according to claim 45, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
95. The reinforced glass-ceramic according to claim 56, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
96. The reinforced glass-ceramic according to claim 65, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
97. The reinforced glass-ceramic according to claim 75, characterized in that Calculated by the molar percentage of each oxide in the reinforced glass-ceramic composition, the composition at the center of the reinforced glass-ceramic satisfies: 1.30≤ZnO / MgO≤2.50; and / or, 0.19≤(Al2O3-(MgO+ZnO)) / SiO2≤0.
60.
98. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
99. The reinforced glass-ceramic according to claim 98, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 13.00mol%≤ZnO+MgO≤17.30mol%; and / or, 10.00mol%≤Al2O3-(MgO+ZnO)≤20.00mol%.
100. The reinforced glass-ceramic according to claim 9, characterized in that: The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
101. The reinforced glass-ceramic according to claim 10, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
102. The reinforced glass-ceramic according to claim 14, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
103. The reinforced glass-ceramic according to claim 18, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
104. The reinforced glass-ceramic according to claim 23, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
105. The reinforced glass-ceramic according to claim 30, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
106. The reinforced glass-ceramic according to claim 37, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
107. The reinforced glass-ceramic according to claim 45, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
108. The reinforced glass-ceramic according to claim 56, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
109. The reinforced glass-ceramic according to claim 65, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
110. The reinforced glass-ceramic according to claim 75, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
111. The reinforced glass-ceramic according to claim 86, characterized in that The composition at the center of the reinforced glass-ceramic also satisfies the following conditions, based on the molar percentage of each oxide in the reinforced glass-ceramic composition: 12.00mol%≤ZnO+MgO≤20.00mol%; and / or, 9.00mol%≤Al2O3-(MgO+ZnO)≤22.00mol%; and / or, 6.82mol%≤Na2O+Li2O≤13.50mol%.
112. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
113. The reinforced glass-ceramic according to claim 9, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
114. The reinforced glass-ceramic according to claim 10, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
115. The reinforced glass-ceramic according to claim 14, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
116. The reinforced glass-ceramic according to claim 18, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
117. The reinforced glass-ceramic according to claim 23, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
118. The reinforced glass-ceramic according to claim 30, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
119. The reinforced glass-ceramic according to claim 37, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
120. The reinforced glass-ceramic according to claim 45, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
121. The reinforced glass-ceramic according to claim 56, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
122. The reinforced glass-ceramic according to claim 65, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
123. The reinforced glass-ceramic according to claim 75, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
124. The reinforced glass-ceramic according to claim 86, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
125. The reinforced glass-ceramic according to claim 98, characterized in that The transmittance of the 0.7 mm thick reinforced glass-ceramic at a wavelength of 550 nm is greater than or equal to 85.00%.
126. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
127. The reinforced glass-ceramic according to claim 126, characterized in that The average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.40 m.
128. The reinforced glass-ceramic according to claim 127, characterized in that The average sandpaper drop resistance height of the reinforced glass ceramic is 1.50m to 2.50m.
129. The reinforced glass-ceramic according to claim 9, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
130. The reinforced glass-ceramic according to claim 10, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
131. The reinforced glass-ceramic according to claim 14, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
132. The reinforced glass-ceramic according to claim 18, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
133. The reinforced glass-ceramic according to claim 23, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
134. The reinforced glass-ceramic according to claim 30, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
135. The reinforced glass-ceramic according to claim 37, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
136. The reinforced glass-ceramic according to claim 45, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
137. The reinforced glass-ceramic according to claim 56, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
138. The reinforced glass-ceramic according to claim 65, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
139. The reinforced glass-ceramic according to claim 75, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
140. The reinforced glass-ceramic according to claim 86, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
141. The reinforced glass-ceramic according to claim 98, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
142. The reinforced glass-ceramic according to claim 112, characterized in that The 0.7 mm thick reinforced glass-ceramic is subjected to a drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the reinforced glass-ceramic is greater than or equal to 1.00 m.
143. The reinforced glass ceramic according to any one of claims 1 to 8, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
144. The reinforced glass-ceramic according to claim 9, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
145. The reinforced glass-ceramic according to claim 10, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
146. The reinforced glass-ceramic according to claim 14, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
147. The reinforced glass-ceramic according to claim 18, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
148. The reinforced glass-ceramic according to claim 23, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
149. The reinforced glass-ceramic according to claim 30, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
150. The reinforced glass-ceramic according to claim 37, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
151. The reinforced glass-ceramic according to claim 45, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
152. The reinforced glass-ceramic according to claim 56, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
153. The reinforced glass-ceramic according to claim 65, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
154. The reinforced glass-ceramic according to claim 75, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
155. The reinforced glass-ceramic according to claim 86, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
156. The reinforced glass-ceramic according to claim 98, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
157. The reinforced glass-ceramic according to claim 112, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
158. The reinforced glass-ceramic according to claim 126, characterized in that The reinforced glass ceramic is obtained by subjecting a chemically reinforced glass ceramic to a chemically reinforced glass ceramic, and the composition of the chemically reinforced glass ceramic is the same as the composition at the center of the reinforced glass ceramic.
159. A glass device made from the reinforced glass ceramic according to any one of claims 1 to 158.
160. An electronic device comprising the reinforced glass ceramic according to any one of claims 1 to 158.
Citation Information
Patent Citations
Ion exchangeable, transparent gahnite-spinel glass ceramics with high hardness and modulus
CN111615500A
Transparent tempered glass ceramic with high stress depth and preparation method and application thereof
CN116409933A